Thermoplastic resin foam and method for producing thermoplastic resin foam
Patent Information
- Application Number
- JP2020217878
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-31
- Filing Date
- 2020-12-25
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-12-25
AI Technical Summary
【0010】 本発明の熱可塑性樹脂発泡体によれば、耐熱強度の向上を図れる。
Smart Images

Figure 0007609634000017 
Figure 0007609634000018 
Figure 0007609634000019
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin foam, a thermoplastic resin foam sheet, a method for producing a thermoplastic resin foam, a thermoplastic resin foam molded product, and a method for producing a thermoplastic resin foam molded product. [Background technology]
[0002] 2. Description of the Related Art Conventionally, resin foam sheets obtained by foaming thermoplastic resins such as polystyrene-based resins and molded articles thereof have been used for food containers and the like because of their characteristics of being lightweight and having high thermal insulation properties. The market for ready-made meals, where prepared foods are purchased from convenience stores, supermarkets, and other retailers and eaten at home, is expanding. In the ready-made meal market, there is a demand for food containers that can be used for cooking in a microwave oven. Food containers that can be used for cooking need to be resistant to deformation when heated in a microwave oven, etc. (excellent dimensional stability when heated) and be easy to handle after heating without becoming soft (excellent heat resistance). For example, Patent Document 1 proposes a method for forming a foamed polyethylene terephthalate (PET) sheet, in which a low-crystallinity foamed PET sheet is preheated to soften the foamed PET sheet, and then molded in a mold at a temperature equal to or higher than that which promotes crystallization. According to the invention of Patent Document 1, the foamed PET sheet is heated to a temperature equal to or higher than that which promotes crystallization, thereby crystallizing the PET and improving the dimensional stability upon heating. However, the invention of Patent Document 1 requires a step (heat setting step) for promoting crystallization, which lengthens the molding time. In addition, the invention of Patent Document 1 requires an apparatus capable of heating to a temperature for promoting crystallization, which has problems such as requiring new capital investment. To address these problems, Patent Document 2 proposes a thermoplastic polyester resin foam sheet containing a specific ratio of a crystalline polyester resin and an amorphous polyester resin having a specific glass transition temperature Tg. According to the invention of Patent Document 2, a container with excellent dimensional stability upon heating can be obtained without requiring a heat setting process. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 3-239527 [Patent Document 2] JP 2014-028920 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the invention of Patent Document 2 has low heat resistance strength, which makes the container soft and weak after heating, making it difficult to handle. Therefore, an object of the present invention is to provide a thermoplastic resin foam having excellent heat resistant strength. [Means for solving the problem]
[0005] As a result of intensive research, the present inventors have found that a mixture of a crystalline polyester resin and an amorphous polyester resin is not sufficiently compatible with each other, and therefore softens and deforms when it reaches the glass transition temperature of the lower of the two polyester resins. Based on this finding, the present inventors have found that the heat resistance can be increased by incorporating two highly compatible resins, and have completed the present invention.
[0006] That is, the present invention has the following aspects. <1> Contains a thermoplastic resin, The thermoplastic resin includes a polyester resin and a polyimide resin, A thermoplastic resin foam with a single glass transition temperature Tg. <2> The glass transition temperature Tg is 80 to 130° C. <1> The thermoplastic resin foam according to claim 1. <3> The absolute value of the difference between the endothermic amount and the exothermic amount determined by heat flux differential scanning calorimetry at a heating rate of 10°C / min is 3 to 35 J / g. <1> or <2> The thermoplastic resin foam according to claim 1. <4> The content of the polyester resin relative to the total mass of the thermoplastic resin is 40 to 95 mass %, The content of the polyimide resin relative to the total mass of the thermoplastic resin is 5 to 60 mass %. <1> ~ <3> 13. The thermoplastic resin foam according to claim 12, <5> the slope of the exponential approximation equation of the storage modulus E' between the glass transition temperature Tg and the glass transition temperature Tg+20°C in solid viscoelasticity measurement at a heating rate of 5°C / min and a frequency of 1 Hz is -0.18 to -0.025; <1> ~ <4> 13. The thermoplastic resin foam according to claim 12, <6> The polyimide resin is a polyetherimide resin. <1> ~ <5> 13. The thermoplastic resin foam according to claim 12, <7> The polyester resin contains a plant-derived polyester resin. <1> ~ <6> 13. The thermoplastic resin foam according to claim 12, <8> The thermoplastic resin comprises recycled materials. <1> ~ <7> 13. The thermoplastic resin foam according to claim 12, <9> It is in sheet form. <1> ~ <8> 13. The thermoplastic resin foam according to claim 12, <10> <9> A thermoplastic resin foam sheet having a layer of the thermoplastic resin foam described in 1.
[0007] <11> A step of extruding and foaming a thermoplastic resin composition containing the thermoplastic resin and a foaming agent to obtain a thermoplastic resin foam. <1> ~ <9> 2. A method for producing a thermoplastic resin foam according to claim 1 . <12> The thermoplastic resin composition further comprises a crosslinking agent. <11> A method for producing the thermoplastic resin foam described in claim 1.
[0008] <13> Contains a thermoplastic resin, The thermoplastic resin includes a polyester resin and a polyimide resin, A thermoplastic resin foam molded product with a single glass transition temperature Tg. <14> The glass transition temperature Tg is 80 to 130° C. <13> The thermoplastic resin foam molded article according to claim 1. <15> The absolute value of the difference between the endothermic amount and the exothermic amount determined by heat flux differential scanning calorimetry at a heating rate of 10°C / min is 3 to 35 J / g. <13> or <14> The thermoplastic resin foam molded article according to claim 1. <16> The content of the polyester resin relative to the total mass of the thermoplastic resin is 40 to 95 mass %, The content of the polyimide resin relative to the total mass of the thermoplastic resin is 5 to 60 mass %. <13> ~ <15> 2. The thermoplastic resin foam molded article according to claim 1 . <17> the slope of the exponential approximation equation of the storage modulus E' between the glass transition temperature Tg and the glass transition temperature Tg+20°C in solid viscoelasticity measurement at a heating rate of 5°C / min and a frequency of 1 Hz is -0.18 to -0.025; <13> ~ <16> 2. The thermoplastic resin foam molded article according to claim 1 . <18> The polyimide resin is a polyetherimide resin. <13> ~ <17> 2. The thermoplastic resin foam molded article according to claim 1 . <19> The polyester resin contains a plant-derived polyester resin. <13> ~ <18> 2. The thermoplastic resin foam molded article according to claim 1 . <20> The thermoplastic resin comprises recycled materials. <13> ~ <19> 2. The thermoplastic resin foam molded article according to claim 1 . <21> A food packaging container. <13> ~ <20> 2. The thermoplastic resin foam molded article according to claim 1 . <22> It is a microwave-compatible container. <13> ~ <21> 2. The thermoplastic resin foam molded article according to claim 1 .
[0009] <23> <1> ~ <9> The thermoplastic resin foam according to any one of the preceding claims, <10> and molding the thermoplastic resin foam or the thermoplastic resin foam sheet to obtain a thermoplastic resin foam molded product. Effect of the Invention
[0010] According to the thermoplastic resin foam of the present invention, it is possible to improve heat resistance strength. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a thermoplastic resin foam according to a first embodiment. [Diagram 2] FIG. 1 is a flow diagram showing an example of a process for producing a plant-derived polyester resin. [Diagram 3] FIG. 1 is a flow diagram showing an example of a process for producing a plant-derived polyester resin. [Figure 4] FIG. 1 is a flow diagram showing an example of a process for producing a plant-derived polyester resin. [Diagram 5] FIG. 1 is a schematic diagram showing an example of a thermoplastic resin foam production apparatus according to a first embodiment. [Figure 6] 1 is a perspective view of a thermoplastic resin foam molded article according to a first embodiment. FIG. [Figure 7] FIG. 1 is a schematic diagram showing an example of a production apparatus for a thermoplastic resin foam molded article. [Figure 8] FIG. 11 is a cross-sectional view showing an example of a thermoplastic resin foam according to a fourth embodiment. [Figure 9] 1 is a graph showing the results of measuring the storage modulus E′ of Example 12. [Figure 10] 1 is a graph showing the results of measuring the storage modulus E′ of Comparative Example 1. [Figure 11] 1 is a DSC curve of Example 12. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In this document, "~" indicates a range that includes both ends of the range as the lower and upper limits.
[0013] The thermoplastic resin foam of the present invention (hereinafter, sometimes simply referred to as "foam") is obtained by foaming a thermoplastic resin composition (hereinafter, sometimes simply referred to as "resin composition") containing a thermoplastic resin and a foaming agent. The form of the foam may be sheet-like, rod-like, or particulate. A non-foamed resin layer may be provided on a part or all of the surface of the foam. For example, the sheet-like foam may be a sheet having a single-layer structure consisting of only a foam layer of the foam, or may have a non-foamed layer provided on one or both sides to form a thermoplastic resin laminated foam sheet (hereinafter, sometimes simply referred to as a "laminated foam sheet"). Hereinafter, a single-layer sheet consisting of only a foam layer of a sheet-like foam and a laminated foam sheet including the same may be collectively referred to as a "thermoplastic resin foam sheet" (foam sheet). The single-layer structure consisting of only a foam layer includes a foam sheet consisting of one foam layer and a foam sheet consisting of two or more foam layers. Hereinafter, the present invention will be described with reference to embodiments thereof.
[0014] First Embodiment A foam according to a first embodiment of the present invention will be described below. The foam according to this embodiment is a sheet-like foam (foam sheet). 1 is used as a base sheet of a thermoplastic resin foam molded product (sometimes simply referred to as a "resin foam molded product"), a flat cushioning material, etc. Examples of the resin foam molded product include containers such as thermoformed products, compressed air molded products, and deep-drawn molded products. 1 is a cross-sectional view of a foamed sheet 2 of the present embodiment. The foamed sheet 2 is composed of one foamed layer 22. The thickness T of the foamed sheet 2 can be determined taking into consideration the application. For example, if the foamed sheet 2 is for molding a container, the thickness T is preferably 0.3 to 5.0 mm, more preferably 0.4 to 3.0 mm, and even more preferably 0.5 to 2.5 mm. When the thickness T is equal to or more than the above lower limit, the impact resistance and rigidity of the container can be improved. When the thickness T is equal to or less than the above upper limit, the moldability of the foamed sheet 2 can be improved.
[0015] The foam layer 22 is a layer formed by foaming a thermoplastic resin composition. The thermoplastic resin composition contains a thermoplastic resin and a foaming agent. The foamed layer 22 formed by foaming the thermoplastic resin composition contains two or more bubbles in a matrix formed of the thermoplastic resin.
[0016] <Thermoplastic resin> The thermoplastic resin of the foam layer 22 contains a polyester-based resin and a polyimide-based resin. By containing both a polyester-based resin and a polyimide-based resin, the foam sheet 2 of the present invention can have increased heat resistance strength.
[0017] <Polyester resin> Examples of polyester resins include polyethylene terephthalate resin (PET), polybutylene terephthalate resin (PBT), polyethylene naphthalate resin (PEN), polyethylene furanoate resin (PEF), polybutylene naphthalate resin (PBN), polytrimethylene terephthalate resin (PTT), copolymers of terephthalic acid, ethylene glycol and cyclohexane dimethanol, and mixtures thereof. As polyester resins, polyethylene terephthalate resin is preferred, and crystalline polyethylene terephthalate resin (C-PET) is more preferred. C-PET is a polyester resin in which the acid component is terephthalic acid and the glycol component is ethylene glycol. The polyester resin may be a polyester resin derived from a petrochemical product, a plant-derived polyester resin such as so-called bio-PET, or a mixture of these. Examples of plant-derived polyester resins include polyethylene terephthalate resins, plant-derived polyethylene furanoate resins, and plant-derived polytrimethylene terephthalate resins. The polyester resin may be made from recycled materials. These polyester resins may be used alone or in combination of two or more.
[0018] Hereinafter, the plant-derived polyester resin will be described. Plant-derived polyester resins are polymers derived from plant materials such as sugar cane and corn. "Derived from plant materials" includes polymers synthesized or extracted from plant materials. For example, "derived from plant materials" includes polymers obtained by polymerizing monomers synthesized or extracted from plant materials. "Monomers synthesized or extracted from plant materials" includes monomers synthesized using compounds synthesized or extracted from plant materials as raw materials. Plant-derived polyester resins include those in which some of the monomers are "derived from plant materials".
[0019] We will explain plant-derived polyester resins using PET and PEF as examples.
[0020] The synthesis reaction of PET is shown in formula (1). PET is synthesized by the dehydration reaction of n moles of ethylene glycol and n moles of terephthalic acid (Benzen-1,4-dicarboxylic acid). The stoichiometric mass ratio in this synthesis reaction is ethylene glycol:terephthalic acid = 30:70 (mass ratio).
[0021] [ka]
[0022] [In formula (1), n is a stoichiometric coefficient (degree of polymerization) and is a number from 250 to 1100.]
[0023] Ethylene glycol is produced industrially by oxidizing ethylene and hydrating it, and terephthalic acid is produced industrially by oxidizing paraxylene. As shown in Figure 2, when ethylene is obtained by the dehydration reaction of plant-derived ethanol (bioethanol), and PET is synthesized from ethylene glycol (bioethanol-derived ethylene glycol) and terephthalic acid derived from petrochemicals, the PET produced is 30% plant-derived by mass. Furthermore, as shown in Figure 3, when paraxylene is obtained by the dehydration reaction of plant-derived isobutanol (bioisobutanol) and PET is synthesized from terephthalic acid synthesized from this paraxylene and ethylene glycol derived from bioethanol, the PET produced is 100% plant-derived PET by mass.
[0024] The synthesis reaction of PEF is shown in formula (2). PEF is synthesized by the dehydration reaction of n moles of ethylene glycol and n moles of 2,5-furandicarboxylic acid.
[0025] [ka]
[0026] [In formula (2), n is a stoichiometric coefficient (degree of polymerization) and is a number from 250 to 1100.]
[0027] Furandicarboxylic acid (FDCA) can be obtained, for example, by dehydrating plant-derived fructose or glucose to obtain hydroxymethylfurfural (HMF), and then oxidizing the HMF. As shown in FIG. 4, when both FDCA and ethylene glycol are plant-derived, the produced PEF is 100% by mass plant-derived PEF.
[0028] The glass transition temperature Tg of the polyester resin is preferably 50 to 100°C, more preferably 60 to 90°C, and even more preferably 70 to 85°C. When Tg is equal to or higher than the lower limit, the heat resistance and dimensional stability upon heating can be further improved. When Tg is equal to or lower than the upper limit, the molding cycle can be shortened to increase productivity and improve moldability. Note that "moldability" refers to, for example, the ability of a foamed sheet to conform to the cavity of a mold and approach a desired shape when the foamed sheet is sandwiched between the molds and thermoformed, and the closer the foamed sheet is to the desired shape, the "better" the moldability.
[0029] The melting point of the polyester resin is preferably 230 to 270° C., more preferably 240 to 260° C., and even more preferably 245 to 255° C. If the melting point is equal to or higher than the lower limit, the heat resistance and the heat dimensional stability can be further improved. If the melting point is equal to or lower than the upper limit, the molding cycle can be shortened to improve productivity and moldability.
[0030] The intrinsic viscosity (IV value) of the polyester resin is preferably 0.5 to 1.5, more preferably 0.6 to 1.3, and even more preferably 0.7 to 1.2. When the IV value is equal to or higher than the lower limit, cell breakage during foaming is suppressed, and the open cell ratio can be further reduced. When the IV value is equal to or lower than the upper limit, the density can be further reduced, the surface can be made smoother, and the beauty of the appearance can be improved. The IV value can be measured according to the method of JIS K7367-5 (2000).
[0031] The number average molecular weight Mn of the polyester resin is from 9,000 to 26,000, preferably from 15,000 to 26,000, and more preferably from 20,000 to 25,000. When Mn is equal to or greater than the lower limit, the cold resistance (i.e., mechanical strength at low temperatures) can be further improved. When Mn is equal to or less than the upper limit, the heat resistance can be further improved.
[0032] The Z-average molecular weight Mz of the polyester resin is 100,000 to 500,000, preferably 150,000 to 450,000, and more preferably 200,000 to 400,000. If Mz is within the above range, the cold resistance (that is, the mechanical strength at low temperatures) can be further improved.
[0033] Mn and Mz can be measured by the following method. [Molecular weight of polyester resin] Take 5 mg of sample from the measurement target, add 0.5 mL of hexafluoroisopropanol (HFIP) and 0.5 mL of chloroform in that order, and shake gently by hand. Leave it for 24 ± 1.0 hours. After confirming that the sample is completely dissolved, dilute it to 10 mL with chloroform and shake gently by hand to mix. Then, filter it with a non-aqueous 0.45 μm chromato disk made by GL Sciences Inc. or a non-aqueous 0.45 μm syringe filter made by Shimadzu GLC Co., Ltd. to obtain the measurement sample. Measure the measurement sample with a chromatograph under the following measurement conditions, and obtain the number average molecular weight Mn and Z average molecular weight Mz of the sample from the standard polystyrene calibration curve prepared in advance.
[0034] [Measuring device] Measurement equipment: Tosoh Corporation's "HLC-8320GPC EcoSEC" gel permeation chromatograph (with built-in RI and UV detectors). [GPC measurement conditions] ·column <Sample side> Guard column = 1x TSK guardcolumn HXL-H (6.0mm x 4.0cm) manufactured by Tosoh Corporation. Measurement column: Tosoh Corporation's TSKgel GMHXL (7.8 mm I.D. x 30 cm) x 2 in series. <Reference side> Two resistance tubes (inner diameter 0.1 mm x 2 m) in series. Column temperature = 40°C. Mobile phase = chloroform. <Dynamic phase flow rate> Sample side pump = 1.0 mL / min. Reference pump = 0.5 mL / min. Detector = UV detector (254 nm). Injection volume = 15 μL. Measurement time = 26 min. Sampling pitch = 500 ms.
[0035] [Standard polystyrene sample for calibration curve] The standard polystyrene samples for the calibration curve are those manufactured by Showa Denko K.K. under the product names "STANDARD SM-105" and "STANDARD SH-75" and have mass average molecular weights Mw of 5,620,000, 3,120,000, 1,250,000, 442,000, 131,000, 54,000, 20,000, 7,590, 3,450, and 1,320. The above standard polystyrene for the calibration curve is grouped into A (5,620,000, 1,250,000, 131,000, 20,000, 3,450) and B (3,120,000, 442,000, 54,000, 7,590, 1,320). A is weighed (2 mg, 3 mg, 4 mg, 4 mg, 4 mg) and dissolved in 30 mL of chloroform. B is weighed (3 mg, 4 mg, 4 mg, 4 mg, 4 mg) and dissolved in 30 mL of chloroform. The standard polystyrene calibration curve is obtained by injecting 50 μL of each of the prepared solutions A and B, and creating a calibration curve (cubic equation) from the retention times obtained after measurement. The number average molecular weight Mn and Z average molecular weight Mz are calculated using the calibration curve.
[0036] The content of the polyester resin in the total mass of the thermoplastic resins contained in the foamed sheet 2 is preferably 40 to 95 mass%, more preferably 50 to 90 mass%, and even more preferably 60 to 80 mass%. When the content of the polyester resin is equal to or more than the lower limit, moldability can be improved. When the content of the polyester resin is equal to or less than the upper limit, heat resistance can be improved.
[0037] <Polyimide resin> The polyimide resin is not particularly limited, but is preferably a polymer containing a cyclic imide group as a repeating unit, and is preferably a polymer having melt moldability. Examples of polyimide-based resins include polyetherimides described in U.S. Pat. No. 4,141,927, Japanese Patent No. 2,622,678, Japanese Patent No. 2,606,912, Japanese Patent No. 2,606,914, Japanese Patent No. 2,596,565, Japanese Patent No. 2,596,566, and Japanese Patent No. 2,598,478, and the like; Examples of the polymers include those described in JP-A-2007-02311, JP-A-09-48852, JP-A-2007-02356, JP-A-2007-02356, JP-A-2007-02357, JP-A-2007-02354 ... The polyimide resin may be made from recycled materials. These polyimide resins may be used alone or in combination of two or more.
[0038] The polyimide resin is preferably, for example, a compound represented by the following formula (3).
[0039] [ka]
[0040] [In the formula (3), R is an aromatic group having 6 to 42 carbon atoms, and R' is at least one divalent organic group selected from the group consisting of a divalent aromatic group having 6 to 30 carbon atoms, an aliphatic group having 2 to 30 carbon atoms, and an alicyclic group having 4 to 30 carbon atoms. p is a number representing a repeating unit.]
[0041] As the polyimide-based resin, a polyetherimide-based resin having a structural unit having an ether bond is preferred from the viewpoint of improving compatibility with polyester-based resins.
[0042] The polyimide resin can be prepared by a conventionally known manufacturing method. For example, it can be obtained by dehydration condensation of either or both of tetracarboxylic acid and its acid anhydride, which are raw materials capable of deriving R in formula (3), and one or more compounds selected from the group consisting of aliphatic primary diamines and aromatic primary diamines, which are raw materials capable of deriving R' in formula (3). Specific examples of the manufacturing method of the polyimide resin include a method of obtaining a polyamic acid and then subjecting it to thermal ring closure. Alternatively, examples of the manufacturing method include a method of chemically closing the ring using an acid anhydride and a chemical ring-closing agent such as pyridine or carbodiimide, and a method of heating the tetracarboxylic anhydride and a diisocyanate capable of deriving R' to decarbonation and polymerization.
[0043] Examples of tetracarboxylic acids include pyromellitic acid, 1,2,3,4-benzenetetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,2',3,3'-biphenyltetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 2,2',3,3'-benzophenonetetracarboxylic acid, bis(2,3-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl)methane, 1,1'-bis(2,3-dicarboxyphenyl)ethane, and 2,2'-bis(3,4-dicarboxyphenyl) Examples of such acid anhydrides include propane, 2,2'-bis(2,3-dicarboxyphenyl)propane, bis(3,4-dicarboxyphenyl)ether, bis(2,3-dicarboxyphenyl)ether, bis(3,4-dicarboxyphenyl)sulfone, bis(2,3-dicarboxyphenyl)sulfone, 2,3,6,7-naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, 1,2,5,6-naphthalenetetracarboxylic acid, 2,2'-bis[(2,3-dicarboxyphenoxy)phenyl]propane, and acid anhydrides thereof.
[0044] Examples of diamines include benzidine, diaminodiphenylmethane, diaminodiphenylethane, diaminodiphenylpropane, diaminodiphenylbutane, diaminodiphenylether, diaminodiphenylsulfone, diaminodiphenylbenzophenone, o, m, p-phenylenediamine, tolylenediamine, xylylenediamine, and aromatic primary diamines having a hydrocarbon group of these aromatic primary diamines as a structural unit, ethylenediamine, 1,2-propanediamine, 1,3-propanediamine, 2,2-dimethyl-1,3-propanediamine, 1,6-hexamethylenediamine, 1,8 Examples of the diamine include 1,9-octamethylenediamine, 1,10-decamethylenediamine, 1,11-undecamethylenediamine, 1,12-dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 1,4-cyclohexanedimethylamine, 2-methyl-1,3-cyclohexanediamine, isophoronediamine, and the like, as well as aliphatic and alicyclic primary diamines having a hydrocarbon group as a structural unit of these aliphatic and alicyclic primary diamines.
[0045] The glass transition temperature Tg of the polyimide resin is preferably 190 to 240° C., more preferably 200 to 230° C., and even more preferably 210 to 220° C. If Tg is equal to or higher than the lower limit, the heat resistance and the heated dimensional stability can be further improved. If Tg is equal to or lower than the upper limit, the molding cycle can be shortened to increase the productivity and improve the moldability.
[0046] The melt flow rate (MFR) of the polyimide resin is preferably 3 to 30 g / 10 min, more preferably 5 to 25 g / 10 min, and even more preferably 7 to 20 g / 10 min. If the MFR is equal to or higher than the lower limit, the molding cycle can be shortened to increase productivity and moldability. If the MFR is equal to or lower than the upper limit, heat resistance and dimensional stability under heat can be further increased. In this specification, MFR is a value at 337° C. and 6.6 kgf, and can be measured in accordance with the method described in ASTM D1238.
[0047] The number average molecular weight of the polyimide resin is preferably 5,000 to 50,000, more preferably 6,000 to 39,000, and even more preferably 7,000 to 27,000. When the number average molecular weight of the polyimide resin is equal to or higher than the lower limit, the impact resistance can be further improved. When the number average molecular weight of the polyimide resin is equal to or lower than the upper limit, the moldability can be further improved. The number average molecular weight of the polyimide resin is determined by gel permeation chromatography (GPC) using polyethylene oxide as a standard substance.
[0048] The content of the polyimide resin in the total mass of the thermoplastic resins contained in the foamed sheet 2 is preferably 5 to 60 mass%, more preferably 10 to 50 mass%, and even more preferably 20 to 40 mass%. When the content of the polyimide resin is equal to or more than the lower limit, the heat resistance can be further improved. When the content of the polyimide resin is equal to or less than the upper limit, the moldability can be further improved.
[0049] [Method for measuring polyimide resin content] When it is necessary to know the content ratio of polyimide-based resin relative to the total mass of thermoplastic resin contained in the foamed sheet 2, the content ratio of polyimide-based resin can be measured by the following method. For example, the foamed sheet 2 is sliced along a direction (planar direction) perpendicular to the thickness direction of the foamed sheet 2 to prepare a thin sample (e.g., a sample having a thickness of 0.2 mm), and the content ratio of polyimide-based resin is measured for this sample as shown below. The following is an example of a method for measuring the content ratio of polyimide-based resin relative to the total mass of a mixed resin of polyester-based resin and polyimide-based resin. Polyethylene terephthalate (PET) is used as the polyester-based resin, and polyetherimide (PEI) is used as the polyimide-based resin.
[0050] The foamed sheet 2 is sliced into 0.2 mm pieces along a direction (planar direction) perpendicular to the thickness direction from the surface of the foamed sheet 2 to prepare a measurement sample. The surface of the measurement sample is subjected to infrared spectroscopy under the following conditions to obtain an infrared absorption spectrum. Measurement equipment: Thermo SCIENTIFIC's Nicolet iS10 Fourier transform infrared spectrophotometer and Thermo SCIENTIFIC's single reflection horizontal ATR Smart-iTR. ATR Crystal: Diamond attached KRS-5 (angle = 42°). ·Measurement method: Single reflection ATR method. ·Measurement wavenumber range: 4000cm -1 ~400cm -1 . Wavenumber dependence of measurement depth: not corrected. · Detector: Deuterated triglycine sulfate (DTGS) detector and KBr beam splitter. ·Resolution: 4cm -1 . -Number of accumulations: 16 (same for background measurement).
[0051] From the obtained infrared absorption spectrum chart, the peak heights of D1410 and D1778 are obtained, and the content of polyimide resin is calculated from the following formula (p) obtained from a calibration curve prepared using a standard sample. Polyimide resin content (mass%) = 100 - {19.00ln(R) + 37.95} × 100 (p) R=D1410 / D1778
[0052] D1410 is a polyester resin with a wave number of 1410 cm -1 ±5cm -1 The maximum absorbance difference (measured absorbance - baseline absorbance) from the baseline in the infrared absorption spectrum curve in the region of 1400 cm. The baseline is the wave number of 1400 cm in the infrared absorption spectrum curve. -1 ±5cm -1 The position of the minimum absorption at 1420 cm in the infrared absorption spectrum curve -1 ±5cm -1It is a straight line connecting the position of minimum absorption at D1778 is a polyimide resin with a wave number of 1778 cm -1 ±5cm -1 The maximum absorbance difference (measured absorbance - baseline absorbance) from the baseline in the infrared absorption spectrum curve in the region of 1760 cm -1 ±5cm -1 The position of the minimum absorption at 1800 cm and the wave number in the infrared absorption spectrum curve -1 ±5cm -1 It is a straight line connecting the position of minimum absorption at
[0053] [Creating standard samples] The standard samples were prepared as follows. First, according to the formulation shown in Table 1, a polyester resin (PET: manufactured by Far East New Century Co., Ltd., product name "CH-653"), a polyimide resin (PEI: manufactured by SABIC Innovative Plastics, product name "Ultem1000"), and a crosslinking agent, pyromellitic anhydride (PMDA), are mixed to prepare a mixture. This mixture is charged into a Labo Plastomill twin-screw extruder (manufactured by Toyo Seiki Seisakusho Co., Ltd., model: 2DC15W, aperture 15 mm, L / D = 17) and melt-kneaded at 350 ° C to obtain a resin composition. The resin melt is extruded from a nozzle die (diameter 3.0 mm) attached to the front end of the Labo Plastomill twin-screw extruder. The extruded resin composition is immediately cooled in a cooling water tank. Then, the cooled strand-shaped resin composition is thoroughly drained, and then cut into small pellets with a length of about 2 mm and a diameter of about 3 mm using a pelletizer to prepare standard samples (A to I). The compositions of the standard samples (A to I) are shown in Table 1.
[0054] [Table 1]
[0055] [Creating a calibration curve] The calibration curve is prepared as follows. The surfaces of the standard samples (A to I) are subjected to infrared spectroscopic analysis under the following conditions to obtain infrared absorption spectra. Measurement equipment: Thermo SCIENTIFIC's Nicolet iS10 Fourier transform infrared spectrophotometer and Thermo SCIENTIFIC's single reflection horizontal ATR Smart-iTR. ATR Crystal: Diamond attached KRS-5 (angle = 42°). ·Measurement method: Single reflection ATR method. ·Measurement wavenumber range: 4000cm -1 ~400cm -1 . Wavenumber dependence of measurement depth: not corrected. · Detector: Deuterated triglycine sulfate (DTGS) detector and KBr beam splitter. ·Resolution: 4cm -1 . -Number of accumulations: 16 (same for background measurement). Number of measurements: 10.
[0056] From the infrared absorption spectrum chart obtained in each measurement, data processing is performed in the same manner as in the measurement method of the content ratio of the polyimide resin described above, the peak heights of D1410 and D1778 are obtained, and the absorbance ratio (R = D1410 / D1778) is calculated. The blending ratio of the polyester resin against the absorbance ratio of each standard sample (A to I) is plotted, and the logarithmic approximation formula in the plot is used as the calibration curve.
[0057] The thermoplastic resin contained in the foamed sheet 2 may contain recycled raw materials. Either the polyester-based resin or the polyimide-based resin may contain recycled raw materials, or both the polyester-based resin and the polyimide-based resin may contain recycled raw materials. A part or all of the polyester-based resin may be recycled raw materials for polyester-based resin, or a part or all of the polyimide-based resin may be recycled raw materials for polyimide-based resin. Examples of recycled raw materials include the following raw materials: 1) The foam is crushed to obtain flake-like resin, which is then remelted in an extruder and extruded in the form of strands from a nozzle die. After cooling, these are pelletized to produce recovered pellets. 2) Recycled PET made by crushing PET bottles to obtain flake-like resin, which is then remelted in an extruder and extruded into strands through a nozzle die, which are then cooled and pelletized.
[0058] Other resins The foamed sheet 2 is substantially free of thermosetting resin. "Substantially free" means that the thermosetting resin is not contained at all or is contained to an extent that does not affect the quality of the foamed sheet 2. The content of the thermosetting resin in the foamed sheet 2 is preferably 5% by mass or less, more preferably 2% by mass or less, even more preferably 1% by mass or less, and most preferably 0% by mass, based on 100 parts by mass of the thermoplastic resin.
[0059] The thermoplastic resin may include a thermoplastic resin (other thermoplastic resin) other than the polyester resin and the polyimide resin. Examples of the other thermoplastic resin include polyolefin resins such as polyethylene and polypropylene, polystyrene resins, polyphenylene ether resins, polyamide resins, polycarbonate resins, polyarylate resins, polyphenylsulfone resins, polysulfone resins, and polyethersulfone resins.
[0060] The total proportion of the polyester resin and the polyimide resin relative to the total mass of the thermoplastic resin is preferably 90 mass% or more, more preferably 95 mass% or more, even more preferably 98 mass% or more, and most preferably 100 mass%. When the total proportion of the polyester resin and the polyimide resin is equal to or more than the lower limit, the heat resistance of the foamed sheet 2 can be further increased.
[0061] <Physical Properties> The foamed sheet 2 has a single glass transition temperature Tg. The polyester resin and the polyimide resin are compatible with each other, resulting in a single glass transition temperature Tg. Since the foamed sheet 2 has a single glass transition temperature Tg, the glass transition temperature Tg is higher than the glass transition temperature Tg of the polyester resin, resulting in increased heat resistance. The term "single glass transition temperature" means that the glass transition temperature Tg can be recognized as a single temperature on the lower side than the crystallization peak observed in the second heating process in a heat flux differential scanning calorimetry chart (DSC curve) at a heating rate of 10°C / min. However, if no crystallization peak is observed in the second heating process, it means that the glass transition temperature Tg can be recognized as a single temperature range (30 to 300°C) in the second heating process. The glass transition temperature Tg of the foamed sheet 2 is, for example, preferably 80 to 130° C., more preferably 85 to 125° C., and even more preferably 90 to 120° C. When Tg is equal to or higher than the lower limit, the heat resistance and the dimensional stability upon heating can be further improved. When Tg is equal to or lower than the upper limit, the molding cycle can be shortened to increase the productivity and the moldability can be improved. The glass transition temperature Tg of the foamed sheet 2 is determined by heat flux differential scanning calorimetry at a heating rate of 10° C. / min. The glass transition temperature Tg of the foamed sheet 2 can be regarded as the same as the glass transition temperature Tg of the thermoplastic resin constituting the foamed sheet 2.
[0062] The absolute value of the difference between the amount of heat absorbed and the amount of heat generated in the foamed sheet 2 (endothermic heat generation difference) is preferably 3 to 35 J / g, more preferably 5 to 30 J / g, and even more preferably 7 to 28 J / g. When the endothermic heat generation difference is equal to or greater than the lower limit, the degree of crystallization is increased, and the heat resistant strength and dimensional stability under heat can be further improved. When the endothermic heat generation difference is equal to or less than the upper limit, the degree of crystallization does not increase too much, and moldability can be improved. The endothermic heat release difference is the difference between the amount of heat absorbed and the amount of heat released, as determined by heat flux differential scanning calorimetry at a heating rate of 10° C. / min. The heat absorption / heat generation difference in the foamed sheet 2 can be regarded as the same as the heat absorption / heat generation difference of the thermoplastic resin constituting the foamed sheet 2.
[0063] In the foamed sheet 2, the slope r of the exponential approximation equation of the storage modulus E' between the glass transition temperature Tg and the glass transition temperature Tg+20°C in the solid viscoelasticity measurement at a heating rate of 5°C / min and a frequency of 1 Hz (hereinafter, sometimes simply referred to as "slope r") is preferably -0.18 to -0.025, more preferably -0.15 to -0.030, and further preferably -0.10 to -0.035. When the slope r is equal to or greater than the lower limit, the change in the storage modulus E' with increasing temperature is small, and the heat resistant strength can be further improved. When the slope r is equal to or less than the upper limit, the change in the storage modulus E' with increasing temperature is not too small, and the moldability can be further improved. The slope r of the exponential approximation equation for the storage modulus E' is the coefficient r of x in the following equation (e).
[0064] y = p × exp(r × x) (e) y: Storage modulus E' (Pa) x: Temperature (℃) p: y value at x=0 (Pa)
[0065] <Foaming agent> Examples of the blowing agent include saturated aliphatic hydrocarbons such as propane, normal butane, isobutane, normal pentane, isopentane, and hexane, ethers such as dimethyl ether, fluorocarbons such as methyl chloride, 1,1,1,2-tetrafluoroethane, 1,1-difluoroethane, and monochlorodifluoromethane, carbon dioxide, and nitrogen, and dimethyl ether, propane, normal butane, isobutane, carbon dioxide, and nitrogen are preferred. These blowing agents may be used alone or in combination of two or more.
[0066] The content of the foaming agent is not particularly limited, but is preferably, for example, 0.1 to 12 parts by mass with respect to 100 parts by mass of the resin.
[0067] <Optional ingredients> The foamed sheet 2 of the present embodiment may contain other components (optional components) in addition to the thermoplastic resin and the foaming agent. Optional components include cell regulators, stabilizers, UV absorbers, colorants, antioxidants, crystallization accelerators, lubricants, crosslinking agents, surfactants, shrinkage inhibitors, flame retardants, and deterioration inhibitors.
[0068] Examples of the crosslinking agent include acid dianhydrides such as pyromellitic anhydride, polyfunctional epoxy compounds, oxazoline compounds, oxazine compounds, etc. By blending a crosslinking agent in the thermoplastic resin composition, cell breakage during foaming is suppressed, and the open cell ratio can be further reduced. The content of the crosslinking agent is preferably, for example, 0.08 to 0.8 parts by mass with respect to 100 parts by mass of the resin.
[0069] The cell regulator is, for example, a mixture of inorganic powder such as talc, silica, etc. These cell regulators increase the closed cell ratio of the foamed layer 22, making it easier to form the foamed layer 22. The content of the cell regulator is preferably, for example, 0.2 to 5 parts by mass with respect to 100 parts by mass of the resin.
[0070] Examples of the stabilizer include calcium zinc-based heat stabilizers, tin-based heat stabilizers, and lead-based heat stabilizers. The content of the stabilizer is preferably, for example, 1 part by mass or less with respect to 100 parts by mass of the resin.
[0071] Examples of the ultraviolet absorbing agent include a cesium oxide-based ultraviolet absorbing agent and a titanium oxide-based ultraviolet absorbing agent. The content of the ultraviolet absorbing agent is preferably, for example, 1 part by mass or less with respect to 100 parts by mass of the resin.
[0072] Examples of the antioxidant include cerium oxide, cerium oxide / zirconia solid solution, cerium hydroxide, carbon, carbon nanotubes, titanium oxide, and fullerene. The content of the antioxidant is preferably, for example, 1 part by mass or less with respect to 100 parts by mass of the resin.
[0073] Examples of colorants include titanium oxide, carbon black, titanium yellow, iron oxide, ultramarine blue, cobalt blue, calcined pigments, metallic pigments, mica, pearl pigments, zinc oxide, precipitated silica, and cadmium red. When the foamed sheet 2 of the present embodiment is used for food containers, it is preferable to select a colorant registered with the Hygienic Council from among the above colorants. The content of the colorant is, for example, preferably 2 parts by mass or less with respect to 100 parts by mass of the resin.
[0074] Examples of the crystallization promoter include silicates, carbon, metal oxides, etc. Examples of silicates include talc, which is hydrated magnesium silicate. Examples of carbon include carbon black, carbon nanofiber, carbon nanotubes, carbon nanohorns, activated carbon, graphite, graphene, coke, mesoporous carbon, glassy carbon, hard carbon, soft carbon, etc., and examples of carbon black include furnace black, acetylene black, ketjen black, and thermal black. Examples of metal oxides include zinc oxide and titanium oxide. The content of the crystallization accelerator is, for example, preferably 3 parts by mass or less with respect to 100 parts by mass of the resin.
[0075] The above-mentioned optional components may each be used alone or in combination of two or more. The total amount of the optional components contained in the foamed layer 22 is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 3 parts by mass, based on the total mass of the foamed layer 22.
[0076] <Physical Properties> The open cell ratio of the foam layer 22 is preferably 20% or less, more preferably 18% or less, and even more preferably 16% or less. When the open cell ratio of the foam layer 22 is equal to or less than the above upper limit, the impact resistance and moldability of the resin foam molded article can be further improved. The open cell ratio of the foam layer 22 can be determined by the method described in JIS K7138:2006 "Rigid plastic foam - Determination of open cell ratio and closed cell ratio".
[0077] The basis weight of the foam layer 22 is, for example, 50 to 900 g / m 2 is preferable, and 100 to 700 g / m 2 More preferably, 150 to 600 g / m 2 is more preferable. When the basis weight of the foam layer 22 is equal to or more than the above lower limit, the impact resistance of the resin foam molded body can be further improved. When the basis weight of the foam layer 22 is equal to or less than the above upper limit, the resin foam molded body can be made lighter. In addition, when the basis weight of the foam layer 22 is equal to or less than the above upper limit, the heating time during hot molding is not too long, and the productivity of the resin foam molded body can be further improved.
[0078] The basis weight of the foam layer 22 can be measured by the following method. Excluding 20 mm from both ends in the width direction of the foam layer 22, five or more pieces of 10 cm x 10 cm are cut out at equal intervals in the width direction, and the mass (g) of each piece is measured to the nearest 0.001 g. The average mass (g) of each piece is calculated by dividing the mass (g) by the mass (g) of the entire foam layer 22 by the mass (g) of the entire foam layer 22. 2 The value converted into the mass per unit area is the basis weight (g / m) of the foam layer 22. 2 )
[0079] The apparent density of the foam layer 22 is, for example, 0.050 to 0.666 g / cm 3 is preferable, and 0.066 to 0.500 g / cm 3 More preferably, 0.100 to 0.400 g / cm 3 When the apparent density of the foam layer 22 is equal to or higher than the above lower limit, the heat insulating property and impact resistance of the resin foam molded body can be further improved. When the apparent density of the foam layer 22 is equal to or lower than the above upper limit, the resin foam molded body can be made lighter.
[0080] The expansion ratio of the foamed layer 22 is, for example, preferably 2 to 30 times, more preferably 3 to 20 times, and further preferably 3.5 to 15 times. When the expansion ratio of the foamed layer 22 is equal to or more than the above lower limit, the heat insulating property and impact resistance of the resin foam molded article can be further improved. When the expansion ratio of the foamed layer 22 is equal to or less than the above upper limit, the moldability of the foamed sheet 2 can be further improved.
[0081] The average bubble diameter of the foamed layer 22 is, for example, preferably 80 to 1000 μm, more preferably 150 to 750 μm, and even more preferably 200 to 500 μm. When the average bubble diameter of the foamed layer 22 is equal to or greater than the above lower limit, the impact resistance of the resin molded article can be further improved. When the average bubble diameter of the foamed layer 22 is equal to or less than the above upper limit, the surface smoothness of the resin molded article can be further improved. The average cell diameter of the foam layer 22 can be measured in accordance with the method described in ASTM D2842-69.
[0082] <Manufacturing method> The foamed sheet 2 is produced by a conventionally known production method. The foamed sheet 2 can be produced, for example, by the following method. 5 is an apparatus for producing a foamed sheet by extrusion molding. The production apparatus 1 includes an extruder 10, a foaming agent supply source 18, a circular die 20, a mandrel 30, and two winders 40. The extruder 10 is a so-called tandem type extruder. The extruder 10 includes a first extrusion section 11 and a second extrusion section 12 connected to the first extrusion section 11 via a pipe 16. The first extrusion section 11 includes a hopper 14. A foaming agent supply source 18 is connected to the first extrusion section 11. A circular die 20 is connected to the second extrusion section 12. A mandrel 30 having a cutter 32 is provided downstream of the circular die 20. A cooling blower (not shown) is provided between the circular die 20 and the mandrel 30. The extruder 10 of the production apparatus 1 may be an extruder other than a tandem extruder. For example, the extruder 10 may be an extruder in which a circular die 20 is connected to the first extrusion section 11. The extruder 10 of the production apparatus 1 may be a single screw extruder or a multi-screw extruder such as a twin screw extruder.
[0083] The raw material constituting the foamed layer is fed from a hopper 14 to the first extrusion section 11. The raw material fed from the hopper 14 includes the resin constituting the foamed layer, a group of inorganic particles, and optional components that are blended as necessary. In the first extrusion section 11, the raw materials are mixed while being heated to a given temperature to form a resin melt, and a foaming agent is supplied from a foaming agent supply source 18 to the first extrusion section 11, and the foaming agent is mixed with the resin melt to form a resin composition. The heating temperature is appropriately determined in consideration of the type of resin, etc., so long as the resin melts and the optional components are not denatured.
[0084] The glass transition temperature Tg of the polyester resin (raw polyester resin) blended in the thermoplastic resin composition is preferably 50 to 100°C, more preferably 60 to 90°C, and even more preferably 70 to 85°C. When Tg is equal to or higher than the lower limit, the heat resistance and dimensional stability upon heating can be further improved. When Tg is equal to or lower than the upper limit, the molding cycle can be shortened to increase productivity and improve moldability. Note that "moldability" refers to, for example, when a foamed sheet is sandwiched between a mold and thermoformed, the foamed sheet can conform to the mold cavity and approach a desired shape, and the closer to the desired shape, the "better" the moldability.
[0085] The melting point of the raw material polyester resin is preferably 230 to 270° C., more preferably 240 to 260° C., and even more preferably 245 to 255° C. If the melting point is equal to or higher than the lower limit, the heat resistance and the heat dimensional stability can be further improved. If the melting point is equal to or lower than the upper limit, the molding cycle can be shortened to increase the productivity and improve the moldability.
[0086] The intrinsic viscosity (IV value) of the raw material polyester resin is preferably 0.5 to 1.5, more preferably 0.6 to 1.3, and even more preferably 0.7 to 1.2. When the IV value is equal to or higher than the lower limit, cell breakage during foaming can be suppressed, and the open cell ratio can be further reduced. When the IV value is equal to or lower than the upper limit, the density can be further reduced, the surface can be made smoother, and the beauty of the appearance can be improved. The IV value can be measured according to the method of JIS K7367-5 (2000).
[0087] The number average molecular weight Mn of the raw material polyester resin is from 9,000 to 26,000, preferably from 15,000 to 26,000, and more preferably from 20,000 to 25,000. When Mn is equal to or greater than the lower limit, the cold resistance (i.e., mechanical strength at low temperatures) can be further improved. When Mn is equal to or less than the upper limit, the heat resistance can be further improved.
[0088] The Z-average molecular weight Mz of the raw material polyester resin is 100,000 to 500,000, preferably 150,000 to 450,000, and more preferably 200,000 to 400,000. If Mz is within the above range, the cold resistance (that is, the mechanical strength at low temperatures) can be further improved.
[0089] The thermoplastic resin composition is supplied from the first extrusion section 11 through the pipe 16 to the second extrusion section 12, where it is further mixed. Thereafter, the resin composition is cooled to a given temperature and then guided to a resin flow path in the circular die 20. The thermoplastic resin composition guided to the resin flow path is extruded from the circular die 20, and the foaming agent causes the composition to foam, forming a cylindrical laminated foamed sheet 2A. The cylindrical laminated foam sheet 2A is guided to the mandrel 30 while being blown with cooling air sent from a cooling blower. The cylindrical laminated foam sheet 2A passes over the outer surface of the mandrel 30, is cooled to a desired temperature, and is cut into two pieces by a cutter 32 to become a foam sheet 2. The foam sheet 2 is wrapped around a guide roll 42 and a guide roll 44, respectively, and is taken up by a winder 40 to become a foam sheet roll 4.
[0090] Examples of the method for producing the laminated foam sheet include a method in which a foam sheet 2 is obtained by the above-mentioned production method, and a non-foamed layer is formed on the surface of the foam sheet by a T-die method, and a method in which a non-foamed layer is formed by a co-extrusion method.
[0091] <Thermoplastic resin foam molded body> The resin foam molded product of the present embodiment is formed by molding a foam sheet 2. Examples of the resin foam molded product include containers such as food trays, cushioning materials used in industrial parts such as electrical products or automobiles, packaging materials, structural parts, and heat insulating materials.
[0092] The container 100 in Fig. 6 is a bowl-shaped container that is a perfect circle in plan view. The container 100 has a circular bottom wall 110 and a side wall 120 that rises from the periphery of the bottom wall 110. The container 100 has an opening 130 that is surrounded by the upper end of the side wall 120. The side wall 120 widens outward as it approaches the upper end. The opening 130 that is surrounded by the upper end of the side wall 120 is a perfect circle in plan view. The bottom wall 110 is formed of a convex portion 112 that is a perfect circle in plan view and that convex toward the opening 130, and an annular recessed portion 114 that surrounds the convex portion 112.
[0093] The thickness of the bottom wall 110 and the side wall 120 of the container 100 (hereinafter sometimes referred to as "wall thickness") is determined taking into consideration the application, etc., and is, for example, preferably 20 to 1000 μm, more preferably 40 to 800 μm, and even more preferably 60 to 600 μm. When the wall thickness of the container 100 is equal to or greater than the above lower limit, the impact resistance of the container 100 can be further improved. When the wall thickness of the container 100 is equal to or less than the above upper limit, the container 100 can be made lighter. Container 100 is suitable as a food packaging container, and is particularly suitable as a microwave compatible container.
[0094] Although the container 100 of this embodiment has a perfect circular shape in plan view, the present invention is not limited to this. The shape of the container in plan view may be an ellipse or a polygon such as a rectangle.
[0095] The container 100 of this embodiment is obtained by molding the foamed sheet 2 of the first embodiment. That is, the container 100 has bubbles in a thermoplastic resin. The container 100 exhibits a single glass transition temperature Tg. The polyester resin and the polyimide resin are compatible with each other, resulting in a single glass transition temperature Tg. Since the container 100 has a single glass transition temperature Tg, the glass transition temperature Tg is higher than the glass transition temperature Tg of the polyester resin, and the heat resistance strength is increased. The glass transition temperature Tg of the container 100 is, for example, preferably 80 to 130° C., more preferably 85 to 125° C., and even more preferably 90 to 120° C. If Tg is equal to or higher than the lower limit, the heat resistance and dimensional stability under heat can be further improved. If Tg is equal to or lower than the upper limit, moldability is improved, and a container with a beautiful appearance can be obtained.
[0096] The endothermic heat generation difference of the container 100 is preferably 3 to 35 J / g, more preferably 5 to 30 J / g, and even more preferably 7 to 28 J / g. If the endothermic heat generation difference is equal to or greater than the lower limit, the degree of crystallization is increased and the dimensional stability upon heating is improved. If the endothermic heat generation difference is equal to or less than the upper limit, the degree of crystallization is not too high and moldability is improved. The endothermic heat release difference is the difference between the amount of heat absorbed and the amount of heat released, as determined by heat flux differential scanning calorimetry at a heating rate of 10° C. / min.
[0097] In the container 100, the slope r is preferably -0.18 to -0.025, more preferably -0.15 to -0.030, and even more preferably -0.10 to -0.035. If the slope r is equal to or greater than the lower limit, the change in the storage modulus E' associated with an increase in temperature is small, and the heat resistant strength can be further improved. If the slope r is equal to or less than the upper limit, the change in the storage modulus E' associated with an increase in temperature is not too small, and the moldability can be further improved.
[0098] <Method for producing resin foam molded body> The container 100 can be manufactured, for example, by heating the foamed sheet 2 and sandwiching it between a female mold (cavity) and a male mold (core) to form it (thermoforming method). An example of a molding apparatus used in the method for manufacturing the container 100 is shown in FIG. The molding apparatus 200 in FIG. 7 includes a shaft 221, a pair of supply rollers 222, a transport conveyor 223, a preheating section 203, a heating mold 204, a cooling mold 205, and a die-cutting machine 224. The preheating section 203 has an upper heating plate 231 and a lower heating plate 232 facing the upper heating plate 231. Instead of the combination of the upper heating plate 231 and the lower heating plate 232, the preheating section 203 may be a heating furnace. The heating mold 204 has a heating cavity 241 and a heating core 242. The heating mold 204 may be a vacuum molding machine, a pressure molding machine, or the like. The cooling mold 205 has a cooling cavity 251 and a cooling core 252 . The heating cavity 241 and the cooling cavity 251 have the same shape, and the heating core 242 and the cooling core 252 have the same shape.
[0099] First, the foamed sheet roll 4 is attached to the shaft 221. The foamed sheet 2 is unwound from the foamed sheet roll 4, and the foamed sheet 2 is intermittently transported in the X direction by a pair of supply rollers 222. The preheating section 203 heats the transported foamed sheet 2 (preheating step). The surface temperature of the foamed sheet 2 immediately after the preheating step is, for example, preferably 90 to 230°C, more preferably 100 to 210°C, and even more preferably 105 to 190°C. If the heating temperature is equal to or higher than the lower limit, the foamed sheet 4 is softened and the moldability is improved. If the heating temperature is equal to or lower than the upper limit, an excessive increase in the crystallinity of the foamed sheet 2 is suppressed, and the moldability is improved. The heating time in the preheating step is preferably from 5 to 90 seconds, more preferably from 10 to 60 seconds, and even more preferably from 15 to 50 seconds.
[0100] Next, the heating mold 204 sandwiches the foamed sheet 2 between the heating cavity 241 and the heating core 242, and molds the foamed sheet 2 while heating it (molding step). The temperature (heating temperature) of the heating mold in the molding step is preferably 30 to 240°C, more preferably 35 to 200°C, and even more preferably 40 to 180°C. If the heating temperature is equal to or higher than the lower limit, the foamed sheet 2 is softened and pressed into the heating cavity 241, thereby improving moldability. If the heating temperature is equal to or lower than the upper limit, the mold releasability of the molded body is improved. The molding time in the molding step is preferably 1 to 10 seconds, more preferably 2 to 8 seconds, and even more preferably 3 to 7 seconds. If the molding time is equal to or higher than the lower limit, the foamed sheet 2 is softened and pressed into the heating cavity 241, thereby improving moldability. The heating dimensional stability is improved. If the molding time is equal to or lower than the upper limit, the time per cycle is shortened, thereby improving productivity.
[0101] The heated mold 204 may further heat the foamed sheet 2 in the heated mold 204 after the molding step (heat setting step). By providing the heat setting step, the crystallinity of the foamed sheet 2 can be increased, and the dimensional stability upon heating can be further improved. The temperature of the heated mold in the heat setting step (heat setting temperature) is preferably 130 to 240°C, more preferably 140 to 220°C, and even more preferably 150 to 200°C. When the heat setting temperature is equal to or higher than the lower limit, the crystallinity of the foamed sheet 2 can be increased, and the dimensional stability upon heating can be further improved. When the heat setting temperature is equal to or lower than the upper limit, the mold releasability of the molded body can be further improved. The heating time in the heat setting step (heat setting time) is preferably 3 to 90 seconds, more preferably 5 to 60 seconds, and even more preferably 7 to 50 seconds. When the heat setting time is equal to or higher than the lower limit, the crystallinity of the foamed sheet 2 can be increased, and the dimensional stability upon heating can be further improved. When the heat setting time is equal to or lower than the upper limit, the time per cycle can be shortened, and the productivity can be improved. Even if the heat setting step is omitted, the foamed sheet 2 of the present embodiment does not lose its heat resistant strength and does not significantly impair its dimensional stability upon heating.
[0102] Next, the heating mold 203 is opened, and the foamed sheet 2 molded into a desired shape is transferred to the position of the cooling mold 205, where the foamed sheet 2 is sandwiched between the cooling cavity 251 and the cooling core 252 (cooling step). The cooling step may be omitted.
[0103] Next, the container 100, which is a resin foam molded body, is cut out from the foam sheet 2 by a die-cutting machine 224.
[0104] In the foam (foam sheet) of this embodiment, the polyester resin and the polyimide resin are compatible with each other, and the thermoplastic resin has a single glass transition temperature, so that the glass transition temperature Tg is higher than the glass transition temperature Tg of the polyester resin, and the heat resistance strength is improved. Therefore, the resin foam molded product obtained by hot molding the foam has excellent heat resistance strength. In addition, the foam of the present embodiment exhibits excellent heat resistance without requiring a heat setting process, thereby improving the productivity of the resin foam molded article. The resin foam molded article of the present embodiment exhibits excellent heat resistance even when the crystallinity is less than 20%. Furthermore, the resin foam molded article of the present embodiment is produced through a heat setting step, so that the degree of crystallinity is increased and the dimensional stability under heating is further improved.
[0105] Second Embodiment A foam according to a second embodiment of the present invention will be described. The foam according to this embodiment is a rod-shaped foam. The rod-shaped foam (rod-shaped foam) is used as a joint material, an elastic sealant backup material, a fishery rope, a core material for a shimenawa rope, a buoyancy material, a packaging cushioning material, etc.
[0106] The rod-shaped foam is produced by foaming a thermoplastic resin composition, which is the same as the thermoplastic resin composition in the first embodiment.
[0107] The shape of the rod-shaped foam may be cylindrical or prismatic. The size of the rod-shaped foam is appropriately determined taking into consideration the application. For example, if it is cylindrical, the diameter of the circular cross section is 0.1 to 10 cm, and the length is 10 to 200 cm.
[0108] The open cell ratio of the rod-shaped foam is similar to that of the foam sheet of the first embodiment. The apparent density of the rod-shaped foam is, for example, 0.050 to 0.666 g / cm 3 is preferable, and 0.066 to 0.500 / cm 3 More preferably, 0.100 to 0.400 g / cm 3 When the apparent density is equal to or higher than the lower limit, the cushioning power can be increased, whereas when the apparent density is equal to or lower than the upper limit, the mechanical strength can be increased. The expansion ratio of the rod-shaped foam is, for example, preferably 2 to 30, more preferably 3 to 20, and even more preferably 3.5 to 15. When the expansion ratio is equal to or higher than the lower limit, the cushioning force can be increased. When the expansion ratio is equal to or lower than the upper limit, the mechanical strength can be increased. The rod-shaped foam has an average cell diameter of, for example, preferably 80 to 1000 μm, more preferably 150 to 750 μm, and even more preferably 200 to 500 μm. When the average cell diameter is equal to or greater than the lower limit, the cushioning power can be increased. When the average cell diameter is equal to or less than the upper limit, the mechanical strength can be increased.
[0109] The rod-shaped foam is produced by a conventionally known production method. Examples of methods for producing rod-shaped foams include a method in which a thermoplastic resin and a foaming agent are supplied to an extruder and melt-kneaded, and the molten thermoplastic resin composition is extruded through holes in a die provided at the tip of the extruder to foam the composition, thereby obtaining a rod-shaped foam.
[0110] Third embodiment A foam according to a third embodiment of the present invention will be described. The foam according to this embodiment is a particulate foam (expanded beads). The expanded beads are used as a raw material for the so-called in-mold foaming method.
[0111] The size of the expanded beads is appropriately selected depending on the application, and the mass average particle diameter of the expanded beads is, for example, 0.5 to 5 mm.
[0112] The open cell ratio of the expanded beads is similar to that of the foamed sheet of the first embodiment. The apparent density of the expanded particles is, for example, 0.027 to 0.675 g / cm 3 is preferable, and 0.045 to 0.45 g / cm 3 More preferably, 0.0675 to 0.27 g / cm 3 When the apparent density is equal to or higher than the lower limit, the cushioning power can be increased, whereas when the apparent density is equal to or lower than the upper limit, the mechanical strength can be increased. The bulk expansion ratio of the expanded beads is, for example, preferably 2 to 50 times, more preferably 3 to 30 times, and even more preferably 5 to 20 times. If the bulk expansion ratio is equal to or higher than the lower limit, the cushioning force can be increased. If the bulk expansion ratio is equal to or lower than the upper limit, the mechanical strength can be increased. The average bubble diameter of the expanded beads is, for example, preferably 5 to 500 μm, more preferably 10 to 400 μm, and even more preferably 20 to 300 μm. When the average bubble diameter is equal to or greater than the lower limit, the cushioning power can be increased. When the average bubble diameter is equal to or less than the upper limit, the mechanical strength can be increased.
[0113] The expanded beads are produced by a conventionally known production method. The expanded beads can be produced, for example, by the following method. 1) A method in which a thermoplastic resin and a foaming agent are fed into an extruder and melt-kneaded, and the molten thermoplastic resin composition is extruded into the air through holes in a die provided at the tip of the extruder to cause foaming, and while being extruded and foamed, the extruded and foamed spherical particles are cut at the same time, and the cut foamed spherical particles are dropped into water and cooled to obtain foamed particles. 2) A method in which a thermoplastic resin and a foaming agent are fed into an extruder and melt-kneaded, and the molten thermoplastic resin composition is extruded into water through holes in a die provided at the tip of the extruder to foam and cool, and the extruded, foamed, and cooled are simultaneously cut to obtain cut, expanded spherical particles. 3) A method in which a thermoplastic resin and a foaming agent are fed into an extruder and melt-kneaded, the molten thermoplastic resin composition is extruded into water through holes in a die provided at the tip of the extruder and cooled, and is cut at the same time as being extruded and cooled to obtain cut spherical expandable particles, and the expandable particles are heated to obtain expanded particles. 4) A method in which a thermoplastic resin is fed into an extruder and melt-kneaded, the molten thermoplastic resin is extruded into the air through holes in a die at the tip of the extruder, cut as it is extruded, the cut spherical resin particles are dropped into water and cooled to obtain resin particles, the resin particles are impregnated with a blowing agent to obtain expandable particles, and the expandable particles are heated to obtain expandable particles. 5) A method in which a thermoplastic resin is fed into an extruder and melt-kneaded, the molten thermoplastic resin is extruded into water through holes in a die at the tip of the extruder and cooled, and cut while being extruded and cooled to obtain spherical resin particles, the resin particles are impregnated with a blowing agent to obtain expandable particles, and the expandable particles are heated to obtain expandable particles. 6) A method in which a thermoplastic resin is fed into an extruder and melt-kneaded, the molten thermoplastic resin is extruded in the form of strands from holes in a die provided at the tip of the extruder, and after extrusion, the resin is guided into water to cool, and after cooling, the resin is cut to a specified length to obtain cylindrical resin particles, the resin particles are impregnated with a blowing agent to obtain expandable particles, and the expandable particles are heated to obtain expandable particles.
[0114] The resin foam molded article of the present embodiment is obtained by foaming and fusing foam particles. Examples of the resin foam molded article of the present embodiment include food packaging containers such as fish boxes and vegetable boxes, and cushioning materials, packaging materials, structural members, and heat insulating materials used in industrial parts such as electrical products and automobiles.
[0115] The resin foam molded product of this embodiment has a single glass transition temperature Tg. The polyester resin and the polyimide resin are compatible with each other, resulting in a single glass transition temperature Tg. The resin foam molded product has a single glass transition temperature Tg, which is higher than the glass transition temperature Tg of the polyester resin, thereby increasing the heat resistance. The glass transition temperature Tg of the resin foam molded product of this embodiment is similar to the glass transition temperature Tg of the container 100 of the first embodiment.
[0116] The endothermic heat generation difference in the resin foam molded product of this embodiment is similar to the endothermic heat generation difference in the container 100 of the first embodiment.
[0117] The inclination r in the resin foam molded product of this embodiment is similar to the inclination r in the container 100 of the first embodiment.
[0118] The open cell ratio of the resin foam molded product of this embodiment is, for example, preferably 20% or less, more preferably 18% or less, and even more preferably 16% or less. When the open cell ratio of the resin foam molded product is equal to or less than the above upper limit, the impact resistance of the resin foam molded product can be further improved. The open cell ratio of the resin foam molded product can be determined by the method described in JIS K7138:2006 "Rigid plastic foam - Determination of open cell ratio and closed cell ratio".
[0119] The apparent density of the resin foam molded body of this embodiment is, for example, 0.027 to 0.675 g / cm 3 is preferable, and 0.045 to 0.45 g / cm 3 More preferably, 0.0675 to 0.27 g / cm 3 When the apparent density of the resin foam molded article is equal to or higher than the above lower limit, the impact resistance of the resin foam molded article can be further improved. When the apparent density of the resin foam molded article is equal to or lower than the above upper limit, the weight of the resin foam molded article can be further reduced.
[0120] The expansion ratio of the resin foam molded product of this embodiment is, for example, preferably 2 to 50 times, more preferably 3 to 30 times, and even more preferably 5 to 20 times. When the expansion ratio of the resin foam molded product is equal to or higher than the above lower limit, the impact resistance of the resin foam molded product can be further improved. When the expansion ratio of the resin foam molded product is equal to or lower than the above upper limit, the mechanical strength of the resin foam molded product can be further improved.
[0121] The resin foam molded product of the present embodiment has an average bubble diameter of, for example, preferably 5 to 500 μm, more preferably 10 to 400 μm, and even more preferably 20 to 300 μm. When the average bubble diameter of the resin foam molded product is equal to or greater than the above lower limit, the impact resistance of the resin foam molded product can be further improved. When the average bubble diameter of the resin foam molded product is equal to or less than the above upper limit, the surface smoothness of the resin foam molded product can be further improved. The average cell diameter of the resin foam molded product can be measured in accordance with the method described in ASTM D2842-69.
[0122] The resin foamed molded article using the foamed beads can be produced by a conventionally known production method. Examples of the method for producing the resin foamed molded article include the following method. 1) A method in which foamed particles (bulk expansion ratio: 2 to 50 times) are filled into a mold, which is then heated to cause secondary expansion and fusion of the foamed particles, and a resin foamed molded article (expansion ratio: 2 to 50 times) is produced by in-mold foam molding (heat molding process). 2) A method in which expanded particles are heated to an arbitrary bulk expansion ratio to form pre-expanded particles (bulk expansion ratio: 2 to 50 times) (pre-expanding step), the pre-expanded particles are filled into a molding die, which is heated to cause secondary expansion of the pre-expanded particles to fuse, and a resin foam molded article (expansion ratio: 2 to 50 times) is formed by in-mold foam molding (heat molding step). Following the heat molding step, the crystallinity of the thermoplastic resin may be increased by further heating (heat setting step).
[0123] According to the foam (expanded beads) of this embodiment, the polyester resin and the polyimide resin are compatible with each other and have a single glass transition temperature, so that the glass transition temperature Tg is higher than the glass transition temperature Tg of the polyester resin, and the heat resistance strength is improved. Therefore, the resin foam molded article obtained from the foam has excellent heat resistance strength. In addition, the foam of the present embodiment exhibits excellent heat resistance without requiring a heat setting process, thereby improving the productivity of the resin foam molded article. The resin foam molded article of the present embodiment exhibits excellent heat resistance even when the crystallinity is less than 20%. Furthermore, the resin foam molded article of the present embodiment is produced through a heat setting step, so that the degree of crystallinity is increased and the dimensional stability under heating is further improved.
[0124] (Fourth embodiment) The fourth embodiment is a modification of the first embodiment. A fourth embodiment of the present invention will now be described. The foam of this embodiment is a laminated foam sheet. The laminated foam sheet 2A in Fig. 8 is used as a base material for a resin foam molded product, a base material for a folding box, or a flat cushioning material, etc. Examples of the resin foam molded product include containers such as thermoformed products, compressed air molded products, and deep-drawn molded products. 8 is a cross-sectional view of a laminated foam sheet 2A of this embodiment. The laminated foam sheet 2A has a foamed layer 22 and a non-foamed layer 21 provided on one surface of the foamed layer 22. The thickness T1 of the laminated foam sheet 2A can be determined taking into consideration the application. For example, if the laminated foam sheet 2A is for molding a container, the thickness T1 is preferably 0.3 to 5.5 mm, more preferably 0.4 to 3.3 mm, and even more preferably 0.5 to 2.7 mm. When the thickness T1 is equal to or greater than the above lower limit, the impact resistance and rigidity of the container can be improved. When the thickness T1 is equal to or less than the above upper limit, the moldability of the laminated foam sheet 2A can be improved.
[0125] The thickness T22 of the foamed layer 22 is the same as the thickness T of the foamed sheet 2. The foam layer 22 is similar to the foam layer 22 according to the first embodiment.
[0126] The thickness T21 of the non-foamed layer 21 is, for example, preferably 5 to 500 μm, more preferably 10 to 300 μm, and even more preferably 15 to 200 μm. When the thickness T21 is equal to or greater than the above lower limit, the impact resistance and rigidity of the container can be improved. When the thickness T21 is equal to or less than the above upper limit, the moldability of the laminated foamed sheet 2A can be improved. The non-foamed layer may be a non-foamed film having a thickness of less than 250 μm, or a non-foamed sheet having a thickness of 250 μm or more. Hereinafter, the non-foamed film and the non-foamed sheet may be collectively referred to as a "non-foamed film / sheet."
[0127] The non-foamed layer 21 is made of a resin mainly composed of a thermoplastic resin, and is a layer in which substantially no bubbles are formed. In addition, the non-foamed layer 21 is a layer in which substantially no bubbles are formed, but the non-foamed layer 21 may contain a small amount of a foaming agent when the non-foamed layer 21 is formed by a co-extrusion method, for example.
[0128] <Thermoplastic resin> Examples of the thermoplastic resin constituting the non-foamed layer 21 include polyester-based resins, polyimide-based resins, polyolefin-based resins, polystyrene-based resins, polyamide-based resins, etc. These resins may be used alone or in combination of two or more. Furthermore, the resin constituting the non-foamed layer 21 may be the same as the resin constituting the foamed layer 22, or may be different.
[0129] Examples of the polyester resin include aromatic polyester resin and aliphatic polyester resin. Examples of aromatic polyester resins include polyethylene terephthalate (PET), glycol-modified polyethylene terephthalate (copolymer of terephthalic acid, ethylene glycol, and cyclohexanedimethanol) (PET-G), polycyclohexylene dimethylene terephthalate (PCT), glycol-modified polycyclohexylene dimethylene terephthalate (PCT-G), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyethylene furanoate (PEF), polybutylene naphthalate (PBN), and polyarylate (PAR). Examples of aliphatic polyester resins include polycaprolactone (PCL), polybutylene succinate (PBS), polyethylene succinate (PES), polyglycolic acid (PGA), polylactic acid (PLA), polyhydroxybutyrate (PHB), polyethylene adipate (PEA), and polybutylene succinate adipate (PBSA). As the polyester-based resin, plant-derived polyethylene terephthalate (bio-PET) and polyethylene furanoate (bio-PEF) may be used. These polyester resins may be used alone or in combination of two or more. Preferred polyester resins include polyethylene terephthalate (PET) and glycol-modified polyethylene terephthalate (PET-G).
[0130] Examples of polyimide-based resins include polyetherimides described in U.S. Pat. No. 4,141,927, Japanese Patent No. 2,622,678, Japanese Patent No. 2,606,912, Japanese Patent No. 2,606,914, Japanese Patent No. 2,596,565, Japanese Patent No. 2,596,566, and Japanese Patent No. 2,598,478, and the like; Examples of the polymers include those described in Japanese Patent Publication Nos. 99171, JP-A-9-48852, JP 2565556, 2564636, 2564637, 2563548, 2563547, 2558341, 2558339, and 2834580. As long as the effects of the present invention are not impaired, the main chain of the polyimide resin may contain structural units other than cyclic imide units, such as aromatic, aliphatic, alicyclic, alicyclic ester units, and oxycarbonyl units. These polyimide resins may be used alone or in combination of two or more. A preferred polyimide resin is a polyetherimide resin.
[0131] Examples of the polyolefin resin include polyethylene resin and polypropylene resin. As a polyethylene resin, it has almost no branching in the molecular structure due to the catalytic method (medium-low pressure polymerization method), and has a strength of 942 kg / m 3 High density polyethylene resin (PE-HD) is produced with a density of 910 kg / m or more by introducing comonomers. 3 More than 925kg / m 3 Examples of such polyethylene resins include linear low density polyethylene resins (PE-LLD) produced to have the following density, medium density polyethylene resins (PE-MD) produced to have a density between linear low density polyethylene resins (PE-LLD) and high density polyethylene resins (PE-HD), low density polyethylene resins (PE-LD) produced by high pressure polymerization and having long chain branches in the molecular structure, and very low density polyethylene resins (PE-VLD). As the polyethylene resin, plant-derived polyethylene (bio-PET) may be used. These polyethylene resins may be used alone or in combination of two or more.
[0132] Examples of polypropylene-based resins include block polypropylene (block PP), homopolypropylene (homo PP), and high melt strength polypropylene (HMS-PP). Block PP generally has polyethylene dispersed in homo PP, and further has an EPR phase (ethylene-propylene-rubber phase) surrounding the polyethylene. This type of block PP is produced by polymerizing propylene gas in the first step to obtain homo PP, and then polymerizing EPR in the second step in the presence of ethylene gas. As the polypropylene-based resin, plant-derived polypropylene (bio-PP) may be used. These polypropylene resins may be used alone or in combination of two or more.
[0133] Examples of polystyrene-based resins include homopolymers of styrene-based monomers such as styrene, α-methylstyrene, vinyltoluene, chlorostyrene, ethylstyrene, i-propylstyrene, dimethylstyrene, and bromostyrene, or copolymers thereof; copolymers of styrene-based monomers and vinyl monomers polymerizable therewith, mainly consisting of styrene-based monomers: copolymers of styrene-based monomers and rubber components such as butadiene, and so-called high impact polystyrene, which are mixtures or polymers of homopolymers of styrene-based monomers or copolymers thereof, or copolymers of styrene-based monomers and vinyl monomers and diene-based rubber-like polymers. Examples of vinyl monomers polymerizable with styrene-based monomers include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and cetyl (meth)acrylate, and bifunctional monomers such as (meth)acrylonitrile, dimethyl maleate, dimethyl fumarate, diethyl fumarate, ethyl fumarate, divinylbenzene, and alkylene glycol dimethacrylate. These vinyl monomers may be used alone or in combination of two or more. Examples of diene rubber polymers include polybutadiene, styrene-butadiene copolymers, and ethylene-propylene-non-conjugated diene three-dimensional copolymers. As the polystyrene resin, plant-derived polystyrene (bio-PS) may be used. These polystyrene resins may be used alone or in combination of two or more.
[0134] Examples of polyamide resins include nylon 4, nylon 6, nylon 11, nylon 12, and nylon 66. These polyamide resins may be used alone or in combination of two or more. Preferred polyamide resins include nylon 4 and nylon 6.
[0135] Examples of resins (other resins) other than polyester-based resins, polyimide-based resins, polyolefin-based resins, polystyrene-based resins, and polyamide-based resins include ethylene vinyl alcohol (EVOH), polyphenylene ether (PPE), polycarbonate (PC), polyphenylsulfone (PPSU), polysulfone (PSU), polyethersulfone (PESU), and the like. These other resins may be used alone or in combination of two or more.
[0136] <Optional ingredients> The non-foamed layer 21 may contain optional components (optional non-foamed layer components) other than the above-mentioned resins. Examples of optional components of the non-foamed layer include ultraviolet absorbers, antioxidants, colorants, lubricants, flame retardants, antistatic agents, etc. These optional components of the non-foamed layer may be used alone or in combination of two or more.
[0137] <Manufacturing method> The method for producing the laminated foam sheet 2A includes a step of forming the foamed layer 22 (foamed layer forming step) and a step of providing the non-foamed layer 21 on one surface of the foamed layer 22 (lamination step). The laminated foam sheet 2A can be produced by the following method. (1) A method in which a foamed sheet to become foamed layer 22 and a non-foamed film / sheet to become non-foamed layer 21 are separately produced, the non-foamed film / sheet and the foamed sheet are layered in this order, and then heated and pressed together (thermal pressing method). (2) A method in which a non-foamed film / sheet and a foamed sheet are layered in that order and each layer is bonded together with an adhesive (lamination method). (3) A method in which the resin that is the raw material for the non-foamed layer is extruded onto the surface of a foamed sheet through a T-die (T-die method). (4) A method (co-extrusion method) of obtaining a laminate in which a non-foamed layer 21 is provided on a foamed layer 22 by co-extrusion. In the co-extrusion method, the foamed layer forming step and the lamination step are performed in one step.
[0138] In this embodiment, the non-foamed layer is provided on only one side of the foamed layer, but the present invention is not limited to this, and non-foamed layers may be provided on both sides of the foamed layer.
[0139] Fifth embodiment The fifth embodiment is a modification of the first embodiment. A fifth embodiment of the present invention will be described. The foam of this embodiment is a foam sheet consisting of only a foam layer. However, the foam sheet of this embodiment has two or more adjacent foam layers. In addition, each of the foam layers of this embodiment is the foam of the present invention. That is, the foamed sheet of the present embodiment has a first foamed layer and a second foamed layer provided on at least one surface of the first foamed layer.
[0140] The foamed sheet of the present embodiment is used as a base sheet for a resin foam molded product, a base sheet for a folding box, or a flat cushioning material, etc. Examples of the resin foam molded product include containers such as thermoformed products, compressed air molded products, and deep drawn molded products.
[0141] The thickness of the foamed sheet of the present embodiment is determined taking into consideration the use of the foamed sheet, etc. For example, if the foamed sheet is for molding a container, the thickness is preferably 0.3 to 5.0 mm, more preferably 0.4 to 3.0 mm, and even more preferably 0.5 to 2.5 mm. When the thickness is equal to or greater than the above lower limit, the impact resistance and rigidity of the container can be improved. When the thickness is equal to or less than the above upper limit, the moldability of the foamed sheet 2 can be improved.
[0142] Each foam layer in the foam sheet of this embodiment is similar to the foam layers in the first embodiment. The number of foam layers in the foam sheet of the present embodiment is not particularly limited, but is preferably 2 to 4, and more preferably 2 to 3, for example. The densities of the foam layers in the foam sheet of the present embodiment may be the same as or different from each other. The foam layers in the foam sheet of the present embodiment may have the same thickness or different thicknesses. The foam layers in the foam sheet of the present embodiment may have the same basis weight or different basis weights. The closed cell ratios of the foamed layers in the foamed sheet of the present embodiment may be the same as or different from each other. The compositions of the foamed layers in the foamed sheet of the present embodiment may be the same as or different from each other, and therefore the ratio of the polyester resin to the polyimide resin in each foamed layer may be the same as or different from each other.
[0143] <Manufacturing method> The method for producing a foamed sheet of the present embodiment will be described by taking a foamed sheet consisting of two foamed layers as an example. The method for producing a foamed sheet of the present embodiment includes a step of forming a first foamed layer (first foamed layer forming step), a step of forming a second foamed layer (second foamed layer forming step), and a step of providing the second foamed layer on at least one surface of the first foamed layer (lamination step). The first foamed layer forming step and the second foamed layer forming step are the same as the method for producing the foamed sheet 2 in the first embodiment. The lamination step may be carried out in the following manner. (1) A method in which a first foamed sheet to be the first foamed layer and a second foamed sheet to be the second foamed layer are separately produced, the first foamed sheet and the second foamed sheet are stacked in this order, and then heated and pressed together (thermal pressing method). (2) A method in which a first foam sheet and a second foam sheet are superimposed in this order and each layer is bonded to each other with an adhesive (a lamination method). (3) A method of obtaining a laminate in which a second foamed layer is provided on a first foamed layer by coextrusion (coextrusion method). In the coextrusion method, the first foamed layer forming step, the second foamed layer forming step, and the lamination step are performed in one step.
[0144] The foamed sheet of the present embodiment has only two or more foam layers, but the present invention is not limited thereto, and for example, a non-foamed layer may be provided on one or both sides of a foam consisting of two or more foam layers. Alternatively, the foamed sheet of the present invention may have a non-foamed layer provided between each foam layer of a foam consisting of two or more foam layers.
[0145] Sixth embodiment The sixth embodiment is a modification of the first embodiment. A sixth embodiment of the present invention will be described. The foam of this embodiment has a foam layer and a surface material provided on at least one surface of the foam layer. Examples of a method for laminating the foam layer and the surface material include a thermocompression method, a bonding method, a co-extrusion method, and the like.
[0146] The foamed sheet of the present embodiment is used as a raw material for a resin foam molded product, a raw material for a folding box, or a flat cushioning material, etc. Examples of the resin foam molded product include containers such as thermoformed products, compressed air molded products, and deep-drawn molded products, parts of transportation equipment such as automobiles, aircraft, railroad cars, and ships, and cushioning materials and housings for electrical products. Examples of automobile parts include members used near the engine, interior materials, exterior materials, heat insulating materials, and sound absorbing materials.
[0147] Examples of surface materials include fiber-reinforced plastics, cloth, paper, and foam sheets (excluding the foam of the present invention).
[0148] Fiber-reinforced plastics are made by impregnating reinforcing fibers with a synthetic resin for reinforcement. The impregnated synthetic resin for reinforcement can bond and integrate the reinforcing fibers together. The synthetic resin for reinforcement impregnated into the reinforcing fibers may be either a thermoplastic resin or a thermosetting resin, but a thermosetting resin is preferred. The thermosetting resin is not particularly limited, and examples thereof include epoxy resin, unsaturated polyester resin, phenol resin, melamine resin, polyurethane resin, silicon resin, maleimide resin, vinyl ester resin, cyanate ester resin, and resin obtained by prepolymerizing maleimide resin and cyanate ester resin, among which epoxy resin and vinyl ester resin are preferred because of their excellent heat resistance, impact absorption, or chemical resistance. The thermosetting resin may contain additives such as a curing agent and a curing accelerator. The thermosetting resin may be a single type or a combination of two or more types. The thermoplastic resin is not particularly limited, and examples thereof include olefin resins, polyester resins, thermoplastic epoxy resins, amide resins, thermoplastic polyurethane resins, sulfide resins, acrylic resins, etc., and polyester resins and thermoplastic epoxy resins are preferred because they have excellent adhesion to the thermoplastic polyester resin extruded foam sheet or adhesion between the reinforcing fibers constituting the fiber-reinforced plastic layer. The thermoplastic resin may be used alone or in combination of two or more kinds. Examples of the reinforcing fibers constituting the fiber-reinforced plastic layer include inorganic fibers such as glass fibers, carbon fibers, silicon carbide fibers, alumina fibers, Tyranno fibers, basalt fibers, and ceramic fibers; metal fibers such as stainless steel fibers and steel fibers; organic fibers such as aramid fibers, polyethylene fibers, and polyparaphenylene benzoxazole (PBO) fibers; and boron fibers. The reinforcing fibers may be used alone or in combination of two or more. As the reinforcing fibers, carbon fibers, glass fibers, and aramid fibers are preferred, and carbon fibers are more preferred.
[0149] Examples of the fabric include woven fabric and nonwoven fabric. Examples of the fibers constituting the woven fabric and nonwoven fabric include natural fibers and chemical fibers. Examples of the natural fibers include plant fibers such as cotton and hemp, and animal fibers such as silk and wool. Examples of the chemical fibers include regenerated fibers, semi-synthetic fibers, and synthetic fibers. Examples of the regenerated fibers include rayon, cupra, and polynosic. Examples of the semi-synthetic fibers include acetate, triacetate, and promix. Examples of the synthetic fibers include acrylic, polyester, nylon, and polyurethane. These fibers may be used alone or in combination of two or more types.
[0150] Examples of the paper include kraft paper, fine paper, glassine paper, Kent paper, parchment paper, synthetic paper, coated paper, release paper, etc. These papers may be used alone or in combination of two or more kinds.
[0151] Examples of the surface material of the foamed sheet include foamed sheets other than the foamed sheet of the present invention. Examples of the resin constituting the foamed sheet other than the foamed sheet of the present invention include polyester-based resins, polyimide-based resins, polyolefin-based resins, polystyrene-based resins, polyamide-based resins, etc. These resins may be used alone or in combination of two or more. Since they can be laminated with the foamed sheet of the present invention by a thermocompression bonding method or a coextrusion method, polyester-based resins and polyimide-based resins are preferred, and polyethylene terephthalate-based resins and polyetherimide-based resins are more preferred. EXAMPLES
[0152] The present invention will be described below with reference to examples, but the present invention is not limited to these.
[0153] (Raw materials used) <Polyester resin> · PET (A): Manufactured by Far Eastern New Century Co., Ltd., product name "CH-611", glass transition temperature Tg: 78°C, melting point: 251°C, IV value: 1.04, biomass content: 0%. PET (B): Manufactured by INDRAMA, product name "RAMAPET N1B", glass transition temperature Tg: 78°C, melting point: 247°C, IV value: 0.80, biomass content: 30%. PET(C): Manufactured by Far Eastern New Century Co., Ltd., product name "CH-653", glass transition temperature Tg: 79℃, melting point: 248℃, IV value: 1.01, biomass content: 27~30%. PET(D): Manufactured by Far East Ishizuka Green Pet Co., Ltd., product name "CB-603RJ", glass transition temperature Tg: 79℃, melting point: 248℃, IV value: 0.80, biomass content: 0%, recycled PET from PET bottles.
[0154] <Polyimide resin> PEI(A): Polyetherimide, manufactured by SABIC Innovative Plastics, product name "Ultem1000", glass transition temperature Tg: 217°C, MFR: 9g / 10min. PEI (B): Polyetherimide, manufactured by SABIC Innovative Plastics, product name "Ultem 1010", glass transition temperature Tg: 217°C, MFR: 17.8g / 10min. PEI(C): Polyetherimide, manufactured by SABIC Innovative Plastics, product name "Ultem MD130", glass transition temperature Tg: 217°C, MFR: 9g / 10min.
[0155] <Amorphous polyester resin> PCT(G): Eastman Chemical Company, trade name "Traitan TX-1001", aromatic dicarboxylic acid component = terephthalic acid, diol component = 1,4-cyclohexanedimethanol and 2,2,4,4-tetramethyl-1,3-cyclobutanediol, glass transition temperature Tg: 107°C, IV value: 0.72.
[0156] <Talc masterbatch> Talc MB: A masterbatch consisting of 72% PET and 28% talc by mass.
[0157] <Crosslinking agent> · PMDA: Pyromellitic anhydride.
[0158] (Evaluation method) <Thickness> The thickness of the foamed sheet in the width direction (TD direction) except for 20 mm at both ends was measured at nine equally spaced points in the width direction using a dial thickness gauge SM-112 (manufactured by Techlock Corporation), and the arithmetic mean of the measured values was taken as the thickness.
[0159] <Basic weight> Six pieces of 10 cm x 10 cm were cut out at equal intervals in the width direction of the foam sheet, excluding 20 mm at both ends in the width direction (TD direction), and the mass (g) of each piece was measured to the nearest 0.001 g. The average mass (g) of each piece was calculated as 1 m. 2 The converted value is the basis weight (g / m2) of the foam sheet. 2 ) was decided.
[0160] <density> <In the case of foam sheets> The calculation was performed using the following formula (s1) from the basis weight and thickness of the foamed sheet. Apparent density (g / cm 3 ) = basis weight (g / m 2 ) ÷ thickness (mm) ÷ 1000 (s1)
[0161] <In the case of rod-shaped foam> The rod-shaped foam was cut to a predetermined length, and the length of the cut rod-shaped foam was measured. The diameter of the rod-shaped foam was measured at 5 or more equally spaced points in the length direction, and the arithmetic mean of the measured values was taken as the diameter. Next, the mass of the cut rod-shaped foam was measured. It was calculated from the length, diameter, and mass of the rod-shaped foam using the following formula (s2). Apparent density (g / cm 3 ) = mass (g) ÷ (length (cm) × (diameter (cm) / 2) 2 ) × 3.14 (s2)
[0162] <Expansion ratio> The density of the thermoplastic resin was calculated from the blending ratio of each example, and the value obtained by dividing the density of the thermoplastic resin by the apparent density of the obtained foam was taken as the expansion ratio. The following values were used for the density of each resin. PET: 1.35g / cm 3 . PEI: 1.28g / cm 3 . PCT: 1.18g / cm 3 .
[0163] <Open cell ratio> Two or more sheet-like samples measuring 25 mm long x 25 mm wide were cut out from the foam sheet, and the cut out samples were stacked together so that there was no space between them to obtain a test piece with a thickness of 25 mm. The outer dimensions of the test piece were measured to the nearest 1 / 100 mm using a Mitutoyo Corporation "Digimatic Caliper" vernier caliper, and the apparent volume (V1: cm 3 Next, the volume of the test piece (V2: cm3) was measured using a Tokyo Science Co., Ltd. "1000" air comparison specific gravity meter by the 1-1 / 2-1 atmospheric pressure method. 3 ) was calculated. The open cell rate (%) was calculated using the following formula (s3), and the average open cell rate of the five test pieces was calculated. The test pieces were previously conditioned for at least 24 hours in a standard atmosphere of class 2, JIS K 7100:1999, symbol "23 / 50" (temperature 23±2°C, relative humidity 50±5%), and then measured in the same standard atmosphere. The air comparison type specific gravity meter was used with a standard ball (large 28.96 cm 3 , small 8.58cm 3 ) was used for correction. Open cell rate (%) = (V1-V2) / V1 × 100 (s3) (V1: apparent volume measured using a vernier caliper, V2: volume measured using an air comparison hydrometer)
[0164] <Melting point, crystallization temperature, glass transition temperature> The melting point, crystallization temperature and glass transition temperature were measured by the methods described in JIS K7121: 1987 and JIS K7121: 2012. However, the sampling method and temperature conditions were as follows. A sample cut out from the foam or resin foam molded product was packed into the bottom of an aluminum measurement container at 5.5±0.5 mg without leaving any gaps, and then the aluminum lid was placed on the container. Differential scanning calorimetry was then performed using a Hitachi High-Tech Science DSC7000X, AS-3 differential scanning calorimeter. The sample was heated and cooled in the following steps 1 to 4 under a nitrogen gas flow rate of 20 mL / min to obtain a DSC curve. (Step 1) Hold at 30°C for 2 minutes. (Step 2) The temperature is increased from 30°C to 300°C at a rate of 10°C / min (first temperature increase process) and held for 10 minutes. (Step 3) Quickly remove the sample and allow it to cool in an environment of 25±10℃. (Step 4) Heat from 30°C to 300°C at a rate of 10°C / min (second heating process). Alumina was used as the reference material. Using the analysis software attached to the device, the temperatures of the melting peak and the top of the crystallization peak observed during the second heating process were read as the melting point and the crystallization temperature, as shown in Figure 10. The glass transition temperature Tg was calculated from the midpoint glass transition temperature from the DSC curve observed during the second heating process, using the analysis software attached to the device. This midpoint glass transition temperature was obtained from the standard (9.3). The glass transition temperature Tg was determined as the glass transition temperature Tg at a lower temperature than the crystallization peak observed in the second heating process in a heat flux differential scanning calorimetry chart (DSC curve) at a heating rate of 10°C / min. However, if no crystallization peak was observed in the second heating process, the glass transition temperature Tg in the temperature range (30 to 300°C) in the second heating process was used.
[0165] <Solid viscoelasticity measurement> The solid viscoelasticity measurements were performed using an "EXSTRAR DMS6100" viscoelasticity spectrometer manufactured by SII Nano Technology Co., Ltd. Samples were cut out from the foam or resin foam molded body to a length of approximately 40 mm, width of approximately 10 mm, and thickness of approximately 1 mm. The conditions were as follows: Mode: Tensile control mode. Atmosphere: Nitrogen atmosphere. Frequency: 1Hz Heating rate: 5℃ / min. ·Measurement temperature: 30℃~300℃. -Chuck spacing: 20mm. ·Distortion amplitude: 5μm. ·Minimum tension: 100mN. Tension Gain: 1.5 Initial force amplitude: 100mN. The analysis was performed using analysis software provided with the device. As shown in Figures 8 and 9, the slope r was calculated from an exponential approximation equation using the value of the storage modulus E' between the glass transition temperature Tg and the glass transition point Tg + 20°C. Note that Figure 8 shows the measurement results of Example 12 described later, and Figure 9 shows the measurement results of Comparative Example 1 described later. The glass transition temperature Tg was determined from a DSC curve. The dimensions of the test pieces were measured using a "DIGIMATIC" CD-15 type manufactured by Mitutoyo Corporation.
[0166] <Amount of heat absorbed (a), amount of heat generated (b), degree of crystallinity> The endothermic amount (a) (heat of fusion) and the exothermic amount (b) (heat of crystallization) were measured by the methods described in JIS K7121: 1987 and JIS K7121: 2012. However, the sampling method and temperature conditions were as follows. A sample cut out from the foam or resin foam molded product was packed into the bottom of an aluminum measurement container at 5.5±0.5 mg without leaving any gaps, and then the aluminum lid was placed on the container. Differential scanning calorimetry was then performed using a Hitachi High-Tech Science DSC7000X, AS-3 differential scanning calorimeter. The sample was heated and cooled in the following steps 1 and 2 under a nitrogen gas flow rate of 20 mL / min to obtain a DSC curve. (Step 1) Hold at 30°C for 2 minutes. (Step 2) Heat from 30°C to 300°C at a rate of 10°C / min (first heating process). Alumina was used as the reference material. The endothermic amount (a) and the calorific value (b) were calculated using the analysis software attached to the device. Specifically, as shown in Figure 10, the endothermic amount (a) was calculated from the area enclosed by the line connecting the point where the DSC curve leaves the low-temperature baseline and the point where the DSC curve returns to the high-temperature baseline, and the DSC curve. The calorific value (b) was calculated from the area enclosed by the line connecting the point where the DSC curve leaves the low-temperature baseline and the point where the DSC curve returns to the high-temperature baseline, and the DSC curve. The crystallinity was calculated by the following formula (s4) using the endothermic amount (a) and the exothermic amount (b). Degree of crystallinity (%) = {(absolute value of endothermic heat (a) (J / g) - absolute value of exothermic heat (b) (J / g)) ÷ heat of complete crystallization (J / g)} × 100 (s4) The heat of complete crystallization represents the amount of heat required for 100% crystallization. Note that the heat of complete crystallization in the above formula (s4) was 140.1 J / g, which is the heat of complete crystallization of PET.
[0167] (Evaluation method) <Heat resistance strength of foam (heat tensile test)> The tensile modulus in the heat tensile test was measured in accordance with JIS K7127:1999. That is, the tensile modulus was measured using a Shimadzu Corporation "Autograph AG-Xplus 100kN" universal testing machine and a Shimadzu Corporation "TRAPEZIUM X" universal testing machine data processing. The test pieces were dumbbell-shaped type 5, cut out so that their length direction was the extrusion direction (MD). The test speed was 200mm / min, and the gripping distance was 80mm. The test pieces were conditioned for 24 hours or more under the standard atmosphere of JIS K7100:1999 "23 / 50", grade 2, before being used for the test. The measurements were carried out under standard atmosphere (23°C) and 80°C. At 80°C, the test pieces were clamped in a fixture installed in a thermostatic chamber attached to a Shimadzu Corporation "TCR2A type" and held for 1 minute before measurement. The number of test pieces at each of the above-mentioned ambient temperatures was 5, and the arithmetic mean of the tensile modulus measurements for each test piece was taken as the tensile modulus value. The tensile modulus was calculated by setting a region where the slope was maximum within the tensile proportional limit and processing the data from the universal testing machine. The retention rate was calculated by the following formula (s5) using the tensile modulus at 80° C. (E80) and the tensile modulus under standard atmosphere (23° C.) (E23). Retention rate (%)=(E80) / (E23)×100...(s5)
[0168] Evaluation Criteria ◎: Retention rate is 50% or more. ○: Retention rate is between 40% and 50%. △: Retention rate is 25% or more and less than 40%. ×: The retention rate is less than 25%.
[0169] <<Heat dimensional stability of foam (heat deformation test)>> Five flat square test pieces with sides of about 10 cm were cut out from each foam sheet such that each side was parallel to the extrusion direction (MD) or width direction (TD) of the foam sheet. Next, two straight lines were drawn in a cross shape on the foamed sheet layer of each test piece, connecting the center parts of the opposing sides. At this time, the lengths of the straight lines in each direction before heating were designated MD1 and TD1. Next, each test piece was placed on a flat table in an oven without humidity control set at a predetermined temperature, heated for 150 seconds, and then removed from the oven and cooled at room temperature for 30 minutes. Thereafter, the lengths of the straight lines drawn in each direction before heating were measured, and the arithmetic mean value of the measured lengths of each test piece was designated as the length after heating. From the obtained lengths after heating MD2 and TD2 and the lengths before heating MD1 and TD1, the ratio of the length before heating (MD1) to the length after heating (MD2) in the extrusion direction (MD ratio = MD2 / MD1) and the ratio of the length before heating (TD1) to the length after heating (TD2) in the width direction (TD ratio = TD2 / TD1) were calculated.
[0170] Evaluation Criteria ◎: At a temperature setting of 140℃, the smaller of the MD ratio and TD ratio is 0.97 or more. Good: When set at 140°C, the smaller of the MD ratio and TD ratio is less than 0.97, and when set at 120°C, the smaller of the MD ratio and TD ratio is 0.97 or more. △: When set at 140°C, the smaller of the MD ratio and TD ratio was less than 0.97, and when set at 120°C, the smaller of the MD ratio and TD ratio was 0.95 or more and less than 0.97. ×: When set at 140°C, the smaller of the MD ratio and the TD ratio was less than 0.97, and when set at 120°C, the smaller of the MD ratio and the TD ratio was less than 0.95.
[0171] <Impact strength of foam sheet (drop weight impact test)> The total absorbed energy in the drop weight impact test was measured in accordance with ASTM D-3763-15. That is, the total absorbed energy was measured using a drop weight impact tester "CEAST9350" manufactured by CEAST and measurement software "CEAST VIEW". The test piece size was 100 mm in length x 100 mm in width. The number of test pieces was a minimum of 5, and the basis weight of each test piece was within the range of ±5% of the basis weight of the foamed sheet listed in the tables of the Examples and Comparative Examples. The test conditions were as follows.
[0172] <Test conditions> Test speed: 1.76m / sec. - Drop weight: 1.9265kg. · Specimen support span: φ76mm. Tap used: 4.5kN instrumented tap (tip φ12.7mm hemispherical). The test specimens with a test temperature of 23°C were conditioned for 16 hours in an environment according to Procedure A of ASTM D618-13 (23±2°C, relative humidity 50±10%) and used for measurement. The test specimens with a test temperature of -30°C were conditioned for 16 hours in a freezer at a temperature of -30±2°C and used for measurement. The measurement was performed in the same temperature environment as the conditioning. The total absorbed energy of each test specimen was calculated by automatically calculating the integral value of the graph obtained by the measurement using the measurement software. The average value of the total absorbed energy of each test specimen at each test temperature (23°C and -30°C) was taken as the total absorbed energy of the foamed sheet.
[0173] <Evaluation criteria at measurement temperature of 23°C> ◎: Total absorbed energy is 0.50 J or more at a test temperature of 23°C. Good: Total absorbed energy at a test temperature of 23°C is 0.20 J or more and less than 0.50 J. △: Total absorbed energy at a test temperature of 23°C is 0.10 J or more and less than 0.20 J. ×: Total absorbed energy at a test temperature of 23°C is less than 0.10 J.
[0174] <Evaluation criteria at measurement temperature -30℃> ◎: Total absorbed energy is 0.30 J or more at a test temperature of -30°C. Good: Total absorbed energy at a test temperature of -30°C is 0.10 J or more and less than 0.30 J. △: Total absorbed energy at a test temperature of -30°C is 0.05 J or more and less than 0.10 J. ×: Total absorbed energy at a test temperature of -30°C is less than 0.05 J.
[0175] <Overall evaluation of foam sheets> ◎: All items were rated as either "◎" or "〇". ○: There were no "×" marks in the evaluation of any item, and at least one "△" mark in the evaluation of any item. △: There were no "x" marks in the evaluation of any item, and two or more "△" marks in the evaluation of any item. ×: Any of the items was rated as “×”.
[0176] <Heat resistance of container> 100 g of salad oil was placed in each resin foam molded product (container) and heated for 60 seconds in a commercial microwave oven (microwave oven: Panasonic NE1901S type) at an output of 1600 W. Immediately after that, the molded product was lifted up with the salad oil still in it, and the degree of deformation of the molded product was visually evaluated according to the following evaluation criteria.
[0177] Evaluation Criteria ◎: No deformation and can be lifted with one hand. 〇: It deforms a little, but can be lifted with one hand. △: It deforms a lot, but can be lifted with one hand. ×: The deformation is so great that it cannot be lifted with one hand.
[0178] <Moldability> The appearance of the resin foam molded article was visually confirmed and evaluated according to the following evaluation criteria.
[0179] Evaluation Criteria ◎: The shape is formed exactly as in the mold, and even the fine irregularities are sharp, resulting in a beautiful appearance. ◯: The shape is molded according to the die, but the contours of the fine irregularities are slightly blurred. Δ: The shape is slightly different from the shape of the mold, and the contours of the fine irregularities are also blurred, resulting in a poor appearance. ×: The shape is significantly different from the shape of the mold, or tears or holes are found in the molded product.
[0180] <Dimensional stability of containers when heated (heat deformation rate)> The dimensions of the resin foam molded body (container) in the longitudinal direction, transverse direction, and height direction in plan view were calculated. The longitudinal container dimension before heating was, for example, the dimension in the direction in which the distance from one point on the container's contour line in plan view through the center point of the contour shape to the opposite contour line was the longest (distance between container contour lines). The transverse container dimension before heating was, for example, the dimension in the direction in which the distance from one point on the container's contour line in plan view through the center point of the contour shape to the opposite contour line was the shortest (distance between container contour lines). The height container dimension before heating was the distance from the table surface to the bottom of the container when the molded product was placed on a horizontal table with the bottom facing up. The container was then placed on a flat platform in an oven without humidity control, heated at 140°C for 150 seconds, removed, and left in a standard condition (25°C, 1 atm) for 1 hour. The dimensions of the same area were then recorded as the dimensions after heating, and the thermal dimensional change rate was calculated using the following formulas (t1) to (t3). The calculated thermal dimensional change rate was evaluated according to the following evaluation criteria.
[0181] SL=|(L1-L0)| / L0×100···(t1) [SL: rate of change in dimension due to heating in the longitudinal direction (%), L1: longitudinal dimension after heating (mm), L0: longitudinal dimension before heating.] SS=|(L3-L2)| / L2×100···(t2) [SS: Dimensional change rate in the short-side direction due to heating (%), L3: Short-side dimension after heating (mm), L2: Short-side dimension before heating.] ST=|(L5-L4)| / L4×100···(t3) [ST: Heat dimensional change rate in the height direction (%), L5: Height dimension after heating (mm), L4: Height dimension before heating]
[0182] Evaluation Criteria The total heat dimensional deformation rate in each direction (SL+SS+ST) was evaluated according to the following criteria. ⊚: The total heat deformation rate is less than 20%. ◯: The total heat deformation rate is 20% or more and less than 30%. △: The total heat deformation rate is 30% or more and less than 50%. ×: The total heat deformation rate is 50% or more.
[0183] <Overall evaluation of container> : All items were rated as '◎'. Good: All items were rated as either "◎" or "Good", with at least one being "Good". △: There were no "x" marks in the evaluation of any item, and at least one "△" mark in the evaluation of any item. ×: Any of the items was rated as “×”.
[0184] (Examples 1 to 3) According to the formulation in Table 2, PET, PEI, talc MB and a crosslinking agent were mixed in a mixer to prepare a formulation. A die with a diameter of 3 mm and a land length of 5 mm was set at the tip of a single-screw extruder (diameter 40 mm, L / D=40). The extruder was set at a predetermined temperature, and the compound was kneaded in the extruder to obtain a resin melt. A foaming agent (isobutane: normal butane = 35:65 (mass ratio)) was injected from the middle of the extruder barrel, added to the resin melt, and further kneaded to obtain a thermoplastic resin composition. The resin temperature during extrusion was set at 285°C, and the molten thermoplastic resin composition was extruded and foamed from the die at a discharge rate of 7 kg / h to obtain a rod-shaped foam. The physical properties of the obtained rod-shaped foam are shown in Table 2.
[0185] [Table 2]
[0186] As shown in Table 2, a rod-shaped foam was obtained according to the present invention.
[0187] Example 4 According to the formulation in Table 3, PET, PEI, talc MB and a crosslinking agent were mixed in a mixer to prepare a formulation. A circular die with a 93 mm diameter annular slit and a 0.6 mm slit width was set at the tip of a single-screw extruder (bore 65 mm, L / D=34), and a cylindrical cooling mandrel (diameter 206 mm, length 310 mm) was placed in front of the circular die in the extrusion direction. Cooling water was circulated inside the cooling mandrel. The extruder was set to a predetermined temperature, and the compound was kneaded in the extruder to obtain a molten mixture. A foaming agent (isobutane: normal butane = 35:65 (mass ratio)) was pressed into the middle of the extruder barrel and added to the molten resin, which was further kneaded to obtain a thermoplastic resin composition. The resin temperature during extrusion was set to 300°C, and the molten thermoplastic resin composition was extruded and foamed through the die slit of the circular die at a discharge rate of 30 kg / h to form a cylindrical foam. The cylindrical foam was expanded in diameter by a cooling mandrel and taken up by a take-up machine arranged further downstream of the cooling mandrel. The foam was cooled by placing the outer circumferential surface of the cooling mandrel along the inner circumferential surface of the foam, and the cylindrical foam was cut along the extrusion direction downstream of the cooling mandrel. The cylindrical foam was then cut into a flat strip and wound up into a roll by a take-up machine. The physical properties and evaluation of the obtained foam sheet are shown in Table 3.
[0188] (Examples 5 to 9, 11 to 20, Comparative Examples 1 to 4) Foamed sheets were produced in the same manner as in Example 4, except that the resin temperature during extrusion and the take-up speed of the take-up machine were adjusted according to the formulations in Tables 3 to 7. The physical properties and evaluations of the obtained foamed sheets are shown in Tables 3 to 6.
[0189] Example 10 The foamed sheet obtained in Example 9 was pulverized to obtain flake-like resin, which was then remelted in a twin-screw extruder and extruded from a nozzle die in the form of strands. The strands were cooled and then pelletized to produce recovered pellets. A foamed sheet was produced in the same manner as in Example 4, except for using the formulation in Table 4. The physical properties and evaluation of the resulting foamed sheet are shown in Table 4.
[0190] [Table 3]
[0191] [Table 4]
[0192] [Table 5]
[0193] [Table 6]
[0194] [Table 7]
[0195] Examples 4 to 20 in which the present invention was applied were given an overall rating of "△" to "◎". The overall evaluation of Comparative Examples 1 and 2 which did not contain PEI and Comparative Examples 3 and 4 which did not have a single glass transition temperature was "x".
[0196] Example 21 The foamed sheet obtained in Example 12 was cut into a planar square shape with one side of 250 mm. The cut foamed sheet was sandwiched between a pair of hot plates heated to 160° C., and the surface temperature of the foamed sheet was kept at 160° C. for 10 minutes to obtain a heat-set foamed sheet. The physical properties and evaluation of the obtained foamed sheet are shown in Table 8.
[0197] (Example 22, Comparative Examples 5 to 8) A heat-set foamed sheet was obtained in the same manner as in Example 21, except that the foamed sheets shown in Tables 8 to 9 were used and the heat-set conditions shown in Tables 8 to 9 were used. The physical properties and evaluations of the obtained foamed sheets are shown in Tables 8 to 9.
[0198] [Table 8]
[0199] [Table 9]
[0200] The overall evaluation of Examples 21 and 22 in which the present invention was applied was "△" to "◎", and they were particularly excellent in the heat deformation test.
[0201] Example 23 The foamed sheet obtained in Example 12 before heat setting was prepared, and this foamed sheet was cut into a flat square shape with one side of 250 mm. The foamed sheet was set in a frame for fixing the foamed sheet so that the extrusion (MD) direction was the longitudinal direction of the container, and the foamed sheet was preheated in a heater tank at 320°C for 20 seconds to bring the surface temperature of the foamed sheet to 170°C. Thereafter, a tray-shaped molded product (length 210 mm x width 180 mm x height 30 mm) having an opening at the top was obtained by the match mold molding method. The time required to obtain the molded product (molding cycle time) was 33 seconds. The physical properties and evaluation of the obtained molded product are shown in Table 10. The melting point, crystallization temperature and glass transition temperature of the obtained molded product were the same as those of the foamed sheet used and shown in Table 10.
[0202] (Examples 24 to 29, Comparative Examples 9 to 11) Molded articles were obtained in the same manner as in Example 23, except that the foamed sheets shown in Tables 10 to 12 were used and the molding conditions were set to those shown in Tables 10 to 12. The physical properties and evaluations of the obtained molded articles are shown in Tables 10 to 12. The melting point, crystallization temperature, and glass transition temperature of the obtained molded article were the same as the melting point, crystallization temperature, and glass transition temperature of the foamed sheet used, shown in Tables 10-12.
[0203] (Example 30) The foamed sheet obtained in Example 5 before heat setting was prepared, and a flat square test piece with a side length of 34 cm was cut out from the foamed sheet. The test piece was set in a frame for fixing the test piece so that the extrusion (MD) direction of the foamed sheet was the longitudinal direction of the container, and the test piece was preheated in a heater tank at 320°C for 20 seconds to set the surface temperature of the foamed sheet to 170°C. Next, the foamed sheet was vacuum-pressure molded in a mold heated to 180°C, and the molded product was held in the mold for 10 seconds. Thereafter, the mold was opened, and a tray-shaped molded product (length 210 mm x width 180 mm x height 30 mm) with an opening at the top that had been subjected to heat setting was obtained. The physical properties and evaluation of the obtained molded product are shown in Table 12. The melting point, crystallization temperature and glass transition temperature of the obtained molded product were the same as those of the foamed sheet used and shown in Table 12.
[0204] (Examples 31 to 32, Comparative Examples 12 to 16) Molded articles were obtained in the same manner as in Example 30, except that the foamed sheets shown in Tables 12 and 13 were used under the molding conditions shown in Tables 12 and 13. The physical properties and evaluations of the obtained molded articles are shown in Tables 12 and 13. The melting point, crystallization temperature, and glass transition temperature of the obtained molded article were the same as the melting point, crystallization temperature, and glass transition temperature of the foamed sheet used, shown in Tables 12-13.
[0205] [Table 10]
[0206] [Table 11]
[0207] [Table 12]
[0208] [Table 13]
[0209] The overall evaluation of Examples 23 to 32 in which the present invention was applied was from "△" to "◎".
[0210] From the above results, it was confirmed that the application of the present invention can improve the heat resistance strength of a thermoplastic resin foam. In addition, although the heat resistance strength of Comparative Examples 11, 15, and 16 was evaluated as "Fair," the moldability, which is the basic function of a foam, was rated as "Poor," and therefore it was determined that the problems of the present invention were not solved. [Explanation of symbols]
[0211] 2. Foam (foam sheet) 22 Foam layer 100 containers
Claims
1. Contains a thermoplastic resin, The thermoplastic resin includes a polyester resin and a polyetherimide resin, A thermoplastic resin foam having a single glass transition temperature Tg of 80 to 130°C.
2. The thermoplastic resin foam according to claim 1, wherein the absolute value of the difference between the endothermic amount and the exothermic amount determined by heat flux differential scanning calorimetry at a heating rate of 10° C. / min is 3 to 35 J / g.
3. The content ratio of the polyester resin to the total mass of the thermoplastic resin is 40 to 95 mass %, The content ratio of the polyetherimide resin to the total mass of the thermoplastic resin is 5 to 60 mass%. The thermoplastic resin foam according to claim 1 or 2.
4. The thermoplastic resin foam according to any one of claims 1 to 3, wherein the slope of an exponential approximation equation of the storage modulus E' between the glass transition temperature Tg and the glass transition temperature Tg + 20 ° C. in solid viscoelasticity measurement at a heating rate of 5 ° C. / min and a frequency of 1 Hz is -0.18 to -0.
025.
5. The thermoplastic resin foam according to any one of claims 1 to 4, wherein the polyester-based resin comprises a plant-derived polyester-based resin.
6. The thermoplastic resin foam according to any one of claims 1 to 5, wherein the thermoplastic resin comprises recycled materials.
7. The method for producing a thermoplastic resin foam according to any one of claims 1 to 6, further comprising the step of extruding and foaming a thermoplastic resin composition comprising the thermoplastic resin and a foaming agent to obtain a thermoplastic resin foam.
8. The method for producing a thermoplastic resin foam according to claim 7 , wherein the thermoplastic resin composition further contains a crosslinking agent.
Citation Information
Patent Citations
Molding of foamed polymethylene terephthalate sheet
JP1991239527A
Foam and foam particle formed from polyester / polycarbonate resin composition
JP2004182938A
Laminated polyester film
JP2009056621A
Foamed and expandable high glass transition temperature polymers
JP2009521548A
Thermoplastic polyester-based resin extruded foam sheet, molded artifact using the same, method for manufacturing a thermoplastic polyester-based resin extruded foam sheet, and fiber-reinforced composite
JP2014028920A
Cited By
Thermoplastic resin foam, thermoplastic resin foam sheet, fiber-reinforced resin composite, method for manufacturing thermoplastic resin foam, thermoplastic resin foam molded article, method for manufacturing thermoplastic resin foam molded article, and foamed resin composite
EP4190533B1
Thermoplastic resin foam, thermoplastic resin foam sheet, fiber-reinforced resin composite, method for manufacturing thermoplastic resin foam, thermoplastic resin foam molded article, method for manufacturing thermoplastic resin foam molded article, and foamed resin composite
WO2022025274A1